Adhesive dental material kit
By combining dental cleaning materials containing alkali metal halide salts and non-solvent-based dental bonding materials with high water-soluble light-initiating systems, the problem of insufficient durability of dental bonding materials under repeated loads in the prior art is solved, and a dental bonding effect with high initial adhesion and durability is achieved.
Patent Information
- Application Number
- JP2021069143
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-04-15
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2041-04-15
AI Technical Summary
The existing non-solvent-based dental bonding materials have insufficient durability under repeated loads, especially the durability of the bonding interface during chewing.
Dental cleaning materials containing alkali metal halide salts are used in combination with a non-solvent-based dental bonding material containing acidic groups, non-acidic groups and water-soluble light-initiating systems. The solubility of the light initiator system in water is higher than 25°C, and it is able to form a high concentration of light initiator on the surface of the teeth, thereby improving the photocuring rate and intensity of the bonding interface.
The initial adhesion of the tooth surface to the adhesive material is improved, and good adhesion and durability are maintained under repeated loads, reducing the fragility of the adhesive interface.
Smart Images

Figure 0007649681000001 
Figure 0007649681000002 
Figure 0007649681000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an adhesive dental material kit for use in the field of dental care, and more specifically to an adhesive dental material kit comprising as its components a dental cleaning material containing an alkali metal hypochlorite salt, and a non-solvent-based dental adhesive composition which is substantially free of water and organic solvents and in which hardening at the adhesive interface is promoted by contact with a moist body containing moisture. [Background technology]
[0002] In order to repair tooth tissue (enamel, dentin, and cementum) damaged by caries or the like, filling and restorative materials such as filling composite resins and filling compomers; and crown restorative materials such as metal alloys, porcelains, and resin materials are usually used. However, generally, filling and restorative materials and crown restorative materials (both of which may be collectively referred to as "dental restorative materials" in this specification) do not have adhesive properties to tooth tissue. For this reason, various adhesive systems using adhesives have been used to bond tooth tissue and dental restorative materials. As an example of an adhesive system that has been widely used in the past, there is a so-called acid etching type (total etching type) adhesive system in which the surface of tooth tissue is etched using an acid etching material such as an aqueous phosphoric acid solution, and then a dental bonding material, which is an adhesive, is applied to bond tooth tissue and dental restorative materials.
[0003] On the other hand, there is a so-called self-etching adhesive system that does not use an acid etching agent. Conventionally, this adhesive system was mainly a two-step adhesive system in which a self-etching primer containing an acidic monomer, a hydrophilic monomer, and water was applied to the surface of the tooth, and then a dental bonding material containing a cross-linking monomer and a polymerization initiator was applied without rinsing with water, but recently, a one-step adhesive system using a one-liquid dental adhesive (one-liquid dental bonding material) that combines the functions of a self-etching primer and a dental bonding material has been widely used.
[0004] One-liquid dental bonding materials generally contain an acidic monomer, a hydrophilic monomer, a crosslinkable monomer, and the like as monomer components, and water or a hydrophilic volatile organic solvent is generally used.
[0005] However, when a cavity is repaired using such a one-liquid bonding material, it is necessary to remove water or an organic solvent contained in the dental bonding material by air blowing before hardening it. If water or an organic solvent is present, it will cause poor hardening or delayed hardening. Therefore, there has been a growing demand for a non-solvent dental adhesive composition that is substantially free of water and organic solvent, with the aim of omitting the step of air blowing or the like for removing water or organic solvent.
[0006] Recently, self-adhesive dental composite resins that have adhesive properties have been developed, and non-solvent dental adhesive compositions that eliminate the use of dental bonding materials and reduce the number of operational steps in restorative treatment have also begun to be put into practical use.
[0007] In all of the above adhesive systems, a dental bonding material is typically applied to the area to be restored and then light-cured, or, in the case of a self-adhesive dental composite resin, the material is filled in and then light-cured.
[0008] As such an adhesive system, Patent Document 1 proposes a non-solvent-based dental adhesive composition that exhibits high initial adhesive strength, adhesive durability, and dentin cohesive failure rate to tooth tissue (wet body), and that is substantially free of water and organic solvents. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] International Publication No. 2019 / 044815 Summary of the Invention [Problem to be solved by the invention]
[0010] The present inventors have investigated the above-mentioned non-solvent dental adhesive composition and confirmed that the polymerization promotion at the adhesive interface is improved, the initial adhesive strength to dentin and the adhesive durability are improved, and the dominance rate of cohesive failure of the adherend dentin is increased in the observation of the fracture surface after the adhesive test. However, further investigation from an actual clinical point of view has revealed that there is room for improvement in the adhesive durability against repeated load loads, which are assumed to be caused by the force of chewing food.
[0011] Therefore, an object of the present invention is to provide an adhesive dental material kit comprising a dental cleaning material and a non-solvent-based dental adhesive composition, which exhibits high initial adhesive strength to tooth substance (wet body) and also exhibits adhesive durability even under repeated load loading. [Means for solving the problem]
[0012] As a result of extensive research, the present inventors have found that the above-mentioned problems can be solved by a dental cleaning material containing hypochlorite and a non-solvent-based dental adhesive composition containing a specific photopolymerization initiator, and have further researched based on this finding, leading to the completion of the present invention.
[0013] That is, the present invention includes the following inventions. [1] A dental cleaning material (A) containing an alkali metal hypochlorite (a), A non-solvent-based dental adhesive composition (B) containing a monomer (b) having an acidic group, a hydrophobic monomer (c) not having an acidic group, and a water-soluble photopolymerization initiator system (d) having a solubility in water of 10 g / L or more at 25°C; An adhesive dental material kit comprising: [2] The adhesive dental material kit according to [1], wherein the alkali metal hypochlorite (a) contains sodium hypochlorite. [3] The adhesive dental material kit according to [1] or [2], wherein the dental cleaning material (A) comprises an aqueous solution containing 1 to 20 mass % of the alkali metal hypochlorite (a). [4] An adhesive dental material kit described in any of [1] to [3], wherein the water-soluble photopolymerization initiator system (d) contains a water-soluble cleavage-type photopolymerization initiator (d-1) having a solubility in water at 25°C of 10 g / L or more. [5] The adhesive dental material kit according to [4], wherein the water-soluble cleavable photopolymerization initiator (d-1) is at least one selected from the group consisting of compounds represented by general formula (1) and compounds represented by general formula (2). [ka] [ka] [In the formula, R 1 , R 2 , R 3 , R 4 , R 5 , and R 6 are each independently a linear or branched alkyl group having 1 to 4 carbon atoms or a halogen atom, and M is a hydrogen ion, an alkali metal ion, an alkaline earth metal ion, a magnesium ion, a pyridinium ion (the pyridine ring may have a substituent), or HN + Z 1 Z 2 Z 3 (In the formula, Z 1 , Z 2 , and Z 3 are each independently an organic group or a hydrogen atom), and n is 1 or 2. [6] An adhesive dental material kit according to [4] or [5], further comprising a water-insoluble reducing agent (d-3) having a solubility in water of less than 10 g / L at 25°C and a water-insoluble photosensitizer (d-4) having a solubility in water of less than 10 g / L at 25°C. [7] An adhesive dental material kit described in any of [1] to [3], wherein the water-soluble photopolymerization initiator system (d) comprises a water-soluble photosensitizer (d-2) having a solubility in water at 25°C of 10 g / L or more and a water-insoluble reducing agent (d-3) having a solubility in water at 25°C of less than 10 g / L. [8] An adhesive dental material kit described in any of [1] to [3], wherein the water-soluble photopolymerization initiator system (d) comprises a water-insoluble photosensitizer (d-4) having a solubility in water of less than 10 g / L at 25°C and a water-soluble reducing agent (d-5) having a solubility in water of 10 g / L or more at 25°C. [9] An adhesive dental material kit described in any of [1] to [3], wherein the water-soluble photopolymerization initiator system (d) comprises a water-soluble photosensitizer (d-2) having a solubility in water at 25°C of 10 g / L or more and a water-soluble reducing agent (d-5) having a solubility in water at 25°C of 10 g / L or more.
[10] The adhesive dental material kit according to any one of [1] to [9], wherein the non-solvent-based dental adhesive composition (B) further contains a hydrophilic monomer (e) having no acidic group.
[11] The adhesive dental material kit according to
[10] , wherein the content of the hydrophilic monomer (e) not having an acidic group is 50 mass% or less relative to the total mass of the hydrophobic monomer (c) not having an acidic group and the hydrophilic monomer (e) not having an acidic group.
[12] The adhesive dental material kit according to any one of [1] to
[11] , wherein the monomer (b) having an acidic group includes a monomer having a phosphate group.
[13] An adhesive dental material kit according to any one of [1] to
[12] , wherein the non-solvent-based dental adhesive composition (B) further contains a non-water-soluble photopolymerization initiator system (f) having a solubility in water at 25°C of less than 10 g / L.
[14] The adhesive dental material kit according to
[13] , wherein in the non-solvent-based dental adhesive composition (B), the mass ratio [(d):(f)] of the water-soluble photopolymerization initiator system (d) to the water-insoluble photopolymerization initiator system (f) is 10:1 to 1:10.
[15] The adhesive dental material kit according to any one of [1] to
[14] , wherein the non-solvent-based dental adhesive composition (B) is a dental bonding material.
[16] The adhesive dental material kit according to any one of [1] to
[14] , wherein the non-solvent-based dental adhesive composition (B) is a self-adhesive dental composite resin.
[17] The adhesive dental material kit according to any one of [1] to
[14] , wherein the non-solvent-based dental adhesive composition (B) is a dental cement. Effect of the Invention
[0014] According to the present invention, it is possible to provide an adhesive dental material kit comprising a dental cleaning material and a non-solvent-based dental adhesive composition, which exhibits high initial adhesive strength to tooth substance (wet body) and also exhibits adhesive durability even under repeated load loading. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The adhesive dental material kit of the present invention comprises a dental cleaning material (A) and a non-solvent dental adhesive composition (B). The dental cleaning material (A) of the present invention is a composition containing hypochlorite (a). The non-solvent dental adhesive composition (B) of the present invention contains, as essential components, a monomer (b) having an acidic group, a hydrophobic monomer (c) having no acidic group, and a water-soluble photopolymerization initiator system (d) having a solubility in water of 10 g / L or more at 25°C (hereinafter simply referred to as "water-soluble photopolymerization initiator system (d)").
[0016] The adhesive dental material kit of the present invention is used in a procedure in which the area to be restored, i.e., the surface to be adhered, is first cleaned with a dental cleaning material (A), and then the non-solvent-based dental adhesive composition (B) is applied to the area.
[0017] The non-solvent dental adhesive composition (B) of the present invention does not contain a solvent that causes poor curing or delayed curing, i.e., water or an organic solvent, and therefore has the advantage that the step of removing the solvent by air blowing or the like can be omitted when curing it, and that it can be applied as a self-adhesive dental composite resin that has adhesiveness in a dental composite resin that does not contain water or an organic solvent. However, as long as it does not cause inconvenience such as poor curing or delayed curing, the inclusion of a small amount of water or a solvent such as an organic solvent (for example, 3% by mass or less, 1% by mass or less, or 0.1% by mass or less relative to the composition) is acceptable. Therefore, some of the ingredients to be blended are sold in a form containing water or an organic solvent (for example, colloidal silica, etc.), and in such cases, the non-solvent dental adhesive composition (B) of the present invention is prepared by removing the water or organic solvent to the acceptable limit.
[0018] Although no detailed analysis has been conducted on the mechanism by which the adhesive dental material kit of the present invention exhibits high initial adhesive strength to tooth substance (wet body) and further adhesive durability even under repeated load loading, it is speculated as follows.
[0019] The dental cleaning material (A) of the present invention cleans the surface of the tooth to which the non-solvent dental adhesive composition (B) of the present invention is applied. Phosphoric acid etching materials, which are widely known as tooth surface pretreatment materials for dental adhesives, dissolve and remove mineral components constituting the tooth, i.e., hydroxyapatite, to a depth of several microns, and have the effect of significantly changing the component composition and morphology of the surface to be adhered, especially in dentin, but the action of the dental cleaning material (A) of the present invention is different from this. The dental cleaning material (A) of the present invention is applied to the surface to be adhered, and by the oxidizing action of the alkali metal hypochlorite, it oxidizes and decomposes contaminants (especially organic substances) present on the surface of the surface to be adhered and in the area immediately below the surface to remove them. Therefore, unlike phosphoric acid etching materials, it does not dissolve mineral components constituting the tooth, and does not significantly damage the structure of the tooth.
[0020] On the other hand, when the non-solvent dental adhesive composition (B) is applied to the tooth surface, the acidic function of the monomer (b) having an acidic group contained therein dissolves trace amounts of mineral components in the very surface layer of the tooth surface, while the non-solvent dental adhesive composition (B) penetrates into the very surface layer of the tooth surface. Polymerization is then induced by light irradiation, and adhesion is developed between the tooth substance and the hardened product of the non-solvent dental adhesive composition (B).
[0021] In this regard, the non-solvent dental adhesive composition (B) of the present invention improves polymerization hardening at the hydrophilic tooth interface by including the water-soluble photopolymerization initiator system (d). Tooth, especially dentin, contains moisture, so the interface is hydrophilic. In order to increase the adhesive strength to dentin, it is necessary to form a resin-impregnated layer in which the monomer of the dental adhesive composition penetrates the hydrophilic tooth interface, and increase the polymerization rate to form a strong adhesive layer. As described later in this invention, the water-soluble photopolymerization initiator system (d) contained in the non-solvent dental adhesive composition (B) improves the polymerization hardening, and the effect of the dental cleaning material (A) allows the non-solvent dental adhesive composition (B) to penetrate and diffuse on the tooth attachment surface, form a resin-impregnated layer, increase the polymerization rate, and obtain a strong adhesive layer.
[0022] Conventional non-solvent dental adhesive compositions that do not contain solvents, such as self-adhesive dental composite resins, have weak demineralization and penetration effects, and compositions using conventional non-water-soluble photopolymerization initiators have insufficient polymerization rates and only weak resin-impregnated layers are obtained. Therefore, in order to compensate for these shortcomings and form a sufficient resin-impregnated layer, it was necessary to particularly increase the polymerization hardening properties of the adhesive interface and the inside of the resin-impregnated layer. On the other hand, in the non-solvent dental adhesive composition (B) of the present invention, by using the water-soluble photopolymerization initiator system (d), the water-soluble photopolymerization initiator system (d) becomes highly concentrated in the part that comes into contact with the surface of the dentin (wet body) and is locally dissolved in water, and the polymerization hardening properties of the adhesive interface and the inside of the resin-impregnated layer can be selectively increased. As a result, the non-solvent dental adhesive composition (B) of the present invention has high adhesive strength.
[0023] Here, it is considered that the presence of contaminants (particularly organic substances) is an obstacle in the process of the non-solvent dental adhesive composition (B) of the present invention penetrating and diffusing into the tooth structure. By removing the contaminants (particularly organic substances) on the adhesion surface by the action of the dental cleaning material (A) of the present invention, the non-solvent dental adhesive composition (B) reliably penetrates and diffuses into the tooth structure adhesion surface, forming a resin-impregnated layer in which the monomer is impregnated, and by causing polymerization by light irradiation on the resin-impregnated layer, the polymerization rate is increased and a strong adhesive layer is obtained. Therefore, by the action of the dental cleaning material (A), a transition layer with less contaminants, that is, a more homogeneous and high-quality adhesive transition layer, so-called a resin-impregnated layer, is formed between the tooth structure and the hardened product of the non-solvent dental adhesive composition (B), and it is considered that not only the initial adhesive strength but also durable adhesion against repeated load is developed. In this way, it is believed that the combined effects of the dental cleaning material (A) and the non-solvent-based dental adhesive composition (B) result in high initial adhesive strength to tooth substance (wet body) and adhesive durability even under repeated load loading.
[0024] Furthermore, by adjusting the composition of the hydrophobic monomer (c) and the hydrophilic monomer (e) of the non-solvent dental adhesive composition (B) of the present invention, an adhesive dental material kit is provided that exerts the effect of the present invention even on dry tooth tissue. As described above, tooth tissue, particularly dentin, is a wet body containing 12% water, and the surface of the tooth to be restored is usually in a wet state due to the influence of high humidity breath, although it is dried by air blowing after cleaning with the dental cleaning material (A) of the present invention. On the other hand, even in a dry state in which the surface water is removed by air blowing after blocking the influence of breath on the tooth to be restored by mounting a moisture-proof device such as a rubber dam, the tooth exhibits high initial adhesive strength and adhesive durability against repeated load by adjusting the composition of the non-solvent dental adhesive composition (B) described above. In addition, tooth tissue (or dentin) in a "dry state" in this specification refers to a state in which the surface water is sufficiently removed by air blowing.
[0025] The adhesive dental material kit comprising the dental cleaning material (A) and the non-solvent dental adhesive composition (B) of the present invention will be described below with respect to each of the constituent materials and each of the components used therein. In this specification, the upper and lower limits of the numerical ranges (contents of each component, values calculated from each component, and each physical property, etc.) can be appropriately combined. In this specification, "(meth)acrylic" is a general term for methacrylic and acrylic, and the same applies to similar expressions.
[0026] The dental cleaning material (A) of the present invention will be described below.
[0027] The dental cleaning material (A) is a preparation containing an alkali metal hypochlorite (a). The alkali metal hypochlorite (a) used in the present invention includes lithium salt, sodium salt, potassium salt, and cesium salt, among which sodium salt and potassium salt are preferred in terms of stability. Furthermore, it is most preferred that the alkali metal hypochlorite (a) contains sodium hypochlorite. The cleaning effect of the dental cleaning material (A) depends primarily on the concentration of the alkali metal hypochlorite in the aqueous solution of the alkali metal hypochlorite, and the concentration of the alkali metal hypochlorite (a) is preferably 0.1 to 20% by mass, more preferably 1 to 20% by mass. The alkali metal hypochlorite (a) may be used alone or in combination of two or more kinds.
[0028] The dental cleaning material (A) may contain an alkali metal hydroxide compound, typically sodium hydroxide, as a stabilizer. When a stabilizer is added, it is preferable that an alkali metal hydroxide compound, such as sodium hydroxide, is added in an amount of 1 to 20 mass%. The dental cleaning material (A) does not contain an organic compound, such as a monomer.
[0029] The dental cleaning material (A) of the present invention has a BET specific surface area of 10 m to provide formability and improve operability. 2Aluminum oxide fine particles of 0.1 g or more can be added so that the viscosity of the dental cleaning material (A) is preferably 0.05 Pa s or more, more preferably 0.1 Pa s or more. The BET specific surface area of the aluminum oxide can be determined by a specific surface area / pore distribution measuring device based on the gas adsorption method. The viscosity of the dental cleaning material (A) of the present invention can be determined by a rotational viscometer (measurement temperature 37°C: a temperature simulating the temperature inside the oral cavity).
[0030] Each component used in the non-solvent based dental adhesive composition (B) of the present invention will be described below.
[0031] The non-solvent dental adhesive composition (B) is a composition used for repairing tooth structures (enamel, dentin, and cementum) damaged by caries or the like, and contains a monomer (b) having an acidic group, a hydrophobic monomer (c) having no acidic group, and a water-soluble photopolymerization initiator system (d). Each component used in the non-solvent dental adhesive composition (B) of the present invention will be described below.
[0032] <Monomer (b) Having an Acidic Group> The monomer (b) having an acid group has an acid etching effect and a primer treatment effect, and is a component that provides demineralization and penetration. The monomer (b) having an acid group is also polymerizable and provides a hardening effect. By including the monomer (b) having an acid group, the adhesiveness to tooth structure and the adhesive durability are improved.
[0033] Examples of the monomer (b) having an acidic group include a monomer having at least one acidic group such as a phosphoric acid group, a pyrophosphoric acid group, a thiophosphoric acid group, a phosphonic acid group, a sulfonic acid group, a carboxylic acid group, etc., and having at least one polymerizable group such as an acryloyl group, a methacryloyl group, a vinyl group, a styrene group, etc. Specific examples of the monomer (b) having an acidic group are listed below.
[0034] Examples of monomers having a phosphoric acid group include 2-(meth)acryloyloxyethyl dihydrogen phosphate, 3-(meth)acryloyloxypropyl dihydrogen phosphate, 4-(meth)acryloyloxybutyl dihydrogen phosphate, 5-(meth)acryloyloxypentyl dihydrogen phosphate, 6-(meth)acryloyloxyhexyl dihydrogen phosphate, 7-(meth)acryloyloxyheptyl dihydrogen phosphate, 8-(meth)acryloyloxyethyl dihydrogen phosphate, 9-(meth)acryloyloxypropyl dihydrogen phosphate, 10-(meth)acryloyloxybutyl dihydrogen phosphate, 11-(meth)acryloyloxybutyl dihydrogen phosphate, 12-(meth)acryloyloxybutyl dihydrogen phosphate, 13-(meth)acryloyloxypentyl dihydrogen phosphate, 14-(meth)acryloyloxyhexyl dihydrogen phosphate, 15-(meth)acryloyloxyhexyl dihydrogen phosphate, 16-(meth)acryloyloxyhexyl dihydrogen phosphate, 17-(meth)acryloyloxyheptyl dihydrogen phosphate, 18-(meth)acryloyloxyhexyl dihydrogen phosphate, 19-(meth)acryloyloxyhexyl dihydrogen phosphate, 20-(meth)acryloyloxyhexyl dihydrogen phosphate, 21-(meth)acryloyloxyhexyl dihydrogen phosphate, 22-(meth)acryloyloxyhexyl dihydrogen phosphate, 23-(meth)acryloyloxyhexyl dihydrogen phosphate, 24-(meth)acryloyloxyhexyl dihydrogen phosphate, 25-(meth)acryloyloxyhexyl dihydrogen phosphate, 26-(meth)acryloyloxyhexyl dihydrogen phosphate, 27-(meth)acryloyloxyhexyl -(meth)acryloyloxyoctyl dihydrogen phosphate, 9-(meth)acryloyloxynonyl dihydrogen phosphate, 10-(meth)acryloyloxydecyl dihydrogen phosphate, 11-(meth)acryloyloxyundecyl dihydrogen phosphate, 12-(meth)acryloyloxydodecyl dihydrogen phosphate, 16-(meth)acryloyloxyhexadecyl dihydrogen phosphate, 20-(meth)acryloyloxyoctyl dihydrogen phosphate, Examples of suitable hydrogen phosphates include acryloyloxyicosyl dihydrogen phosphate, bis[2-(meth)acryloyloxyethyl]hydrogen phosphate, bis[4-(meth)acryloyloxybutyl]hydrogen phosphate, bis[6-(meth)acryloyloxyhexyl]hydrogen phosphate, bis[8-(meth)acryloyloxyoctyl]hydrogen phosphate, bis[9-(meth)acryloyloxynonyl]hydrogen phosphate, bis[10-(meth)acryloyloxydecyl]hydrogen phosphate, 1,3-di(meth)acryloyloxypropyl dihydrogen phosphate, 2-(meth)acryloyloxyethylphenyl hydrogen phosphate, 2-(meth)acryloyloxyethyl-2-bromoethyl hydrogen phosphate, bis[2-(meth)acryloyloxy-(1-hydroxymethyl)ethyl]hydrogen phosphate, and acid chlorides, alkali metal salts, and ammonium salts thereof.
[0035] Examples of monomers having a pyrophosphate group include bis[2-(meth)acryloyloxyethyl]pyrophosphate, bis[4-(meth)acryloyloxybutyl]pyrophosphate, bis[6-(meth)acryloyloxyhexyl]pyrophosphate, bis[8-(meth)acryloyloxyoctyl]pyrophosphate, bis[10-(meth)acryloyloxydecyl]pyrophosphate, and acid chlorides, alkali metal salts, and ammonium salts thereof.
[0036] Examples of monomers having a thiophosphate group include 2-(meth)acryloyloxyethyl dihydrogenthiophosphate, 3-(meth)acryloyloxypropyl dihydrogenthiophosphate, 4-(meth)acryloyloxybutyl dihydrogenthiophosphate, 5-(meth)acryloyloxypentyl dihydrogenthiophosphate, 6-(meth)acryloyloxyhexyl dihydrogenthiophosphate, 7-(meth)acryloyloxyheptyl dihydrogenthiophosphate, and 8-(meth)acryloyloxyoctyl dihydrogenthiophosphate. Examples of suitable acryloyloxyalkyl groups include acryloyloxyalkyl phosphate, 9-(meth)acryloyloxynonyl dihydrogen thiophosphate, 10-(meth)acryloyloxydecyl dihydrogen thiophosphate, 11-(meth)acryloyloxyundecyl dihydrogen thiophosphate, 12-(meth)acryloyloxydodecyl dihydrogen thiophosphate, 16-(meth)acryloyloxyhexadecyl dihydrogen thiophosphate, 20-(meth)acryloyloxyicosyl dihydrogen thiophosphate, and acid chlorides, alkali metal salts, and ammonium salts thereof.
[0037] Examples of monomers having a phosphonic acid group include 2-(meth)acryloyloxyethyl phenylphosphonate, 5-(meth)acryloyloxypentyl-3-phosphonopropionate, 6-(meth)acryloyloxyhexyl-3-phosphonopropionate, 10-(meth)acryloyloxydecyl-3-phosphonopropionate, 6-(meth)acryloyloxyhexyl-3-phosphonoacetate, 10-(meth)acryloyloxydecyl-3-phosphonoacetate, and acid chlorides, alkali metal salts, and ammonium salts thereof.
[0038] Examples of the monomer having a sulfonic acid group include 2-(meth)acrylamide-2-methylpropanesulfonic acid, styrenesulfonic acid, and 2-sulfoethyl (meth)acrylate.
[0039] The monomer having a carboxylic acid group includes a monomer having one carboxy group in the molecule and a monomer having multiple carboxy groups in the molecule.
[0040] Examples of monomers having one carboxy group in the molecule include (meth)acrylic acid, N-(meth)acryloylglycine, N-(meth)acryloylaspartic acid, O-(meth)acryloyltyrosine, N-(meth)acryloyltyrosine, N-(meth)acryloylphenylalanine, N-(meth)acryloyl-p-aminobenzoic acid, N-(meth)acryloyl-o-aminobenzoic acid, p-vinylbenzoic acid, and 2-(meth)acryloyloxybenzoic acid. Examples of the acryloyloxyethyl group include aromatic acid, 3-(meth)acryloyloxybenzoic acid, 4-(meth)acryloyloxybenzoic acid, N-(meth)acryloyl-5-aminosalicylic acid, N-(meth)acryloyl-4-aminosalicylic acid, 2-(meth)acryloyloxyethyl hydrogen succinate, 2-(meth)acryloyloxyethyl hydrogen phthalate, 2-(meth)acryloyloxyethyl hydrogen maleate, and acid halides thereof.
[0041] Examples of monomers having multiple carboxy groups in the molecule include 6-(meth)acryloyloxyhexane-1,1-dicarboxylic acid, 9-(meth)acryloyloxynonane-1,1-dicarboxylic acid, 10-(meth)acryloyloxydecane-1,1-dicarboxylic acid, 11-(meth)acryloyloxyundecane-1,1-dicarboxylic acid, 12-(meth)acryloyloxydodecane-1,1-dicarboxylic acid, 13-(meth)acryloyloxytridecane-1,1-dicarboxylic acid, 4 ...4-(meth)acryloyloxyhexane-1,1-dicarboxylic acid, 4-(meth)acryloyloxyhexane-1,1-dicarboxylic acid, 4-(meth)acryloyloxyhexane-1,1-dicarboxylic acid, 4-(meth)acryloyloxyhexane-1,1-dicarboxylic acid, 4-(meth)acryloyloxyhexane-1,1-dicarboxylic acid, 4-(meth)acryloyloxyhexane-1,1-dicarboxylic acid, 4-(meth)acryloyloxyhexane-1,1-dicarboxylic acid, 4-(meth)acryloyloxyhexane-1,1-dicarboxylic acid, 4-(meth)acryloyloxyhexane-1,1-dicarboxylic acid, 4-(meth)acryloyloxyhexane Examples of the acid anhydride include 4-(meth)acryloyloxyethyl trimellitate, 4-(meth)acryloyloxyethyl trimellitate anhydride, 4-(meth)acryloyloxybutyl trimellitate, 4-(meth)acryloyloxyhexyl trimellitate, 4-(meth)acryloyloxydecyl trimellitate, 2-(meth)acryloyloxyethyl-3'-(meth)acryloyloxy-2'-(3,4-dicarboxybenzoyloxy)propyl succinate, and acid anhydrides or acid halides thereof.
[0042] Among these monomers (b) having an acidic group, phosphate or pyrophosphate group-containing (meth)acrylic monomers are preferred because they exhibit superior adhesiveness to tooth structure, and phosphate group-containing (meth)acrylic monomers are particularly preferred. Among these, divalent phosphate group-containing (meth)acrylic monomers having an alkyl or alkylene group with 6 to 20 carbon atoms as the main chain in the molecule are more preferred, and divalent phosphate group-containing (meth)acrylic monomers having an alkylene group with 8 to 12 carbon atoms as the main chain in the molecule, such as 10-methacryloyloxydecyl dihydrogen phosphate, are even more preferred, in that they exhibit high demineralization properties in the absence of organic solvents and high adhesiveness.
[0043] The monomer (b) having an acidic group may be used alone or in combination of two or more. From the viewpoint of adhesiveness, the content of the monomer (b) having an acidic group is preferably in the range of 1 to 50 parts by mass, more preferably in the range of 3 to 40 parts by mass, and even more preferably in the range of 5 to 30 parts by mass, based on 100 parts by mass of the total amount of the monomers in the non-solvent-based dental adhesive composition (B).
[0044] <Hydrophobic monomer having no acidic group (c)> As the hydrophobic monomer (c) having no acidic group (hereinafter sometimes simply referred to as "hydrophobic monomer (c)"), a radical monomer having no acidic group and a polymerizable group is preferable, and from the viewpoint of easy radical polymerization, the polymerizable group is more preferably a (meth)acrylic group and / or a (meth)acrylamide group. The hydrophobic monomer (c) having no acidic group means a monomer having a solubility in water of less than 10 g / L at 25°C, and examples thereof include crosslinkable monomers such as bifunctional monomers of aromatic compounds, bifunctional monomers of aliphatic compounds, and trifunctional or higher monomers. The hydrophobic monomer (c) having no acidic group improves the mechanical strength, handling, etc. of the non-solvent dental adhesive composition (B).
[0045] Examples of the aromatic bifunctional monomer include 2,2-bis((meth)acryloyloxyphenyl)propane, 2,2-bis[4-(3-(meth)acryloyloxy-2-hydroxypropoxy)phenyl]propane, 2,2-bis(4-(meth)acryloyloxyethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxypolyethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxydiethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxytriethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxytetraethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxypentaethoxyphenyl)propane, and the like. phenyl)propane, 2,2-bis(4-(meth)acryloyloxydipropoxyphenyl)propane, 2-(4-(meth)acryloyloxydiethoxyphenyl)-2-(4-(meth)acryloyloxyethoxyphenyl)propane, 2-(4-(meth)acryloyloxydiethoxyphenyl)-2-(4-(meth)acryloyloxytriethoxyphenyl)propane, 2-(4-(meth)acryloyloxydipropoxyphenyl)-2-(4-(meth)acryloyloxytriethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxypropoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxyisopropoxyphenyl)propane, and the like. Among these, 2,2-bis[4-(3-methacryloyloxy-2-hydroxypropoxy)phenyl]propane (commonly known as "Bis-GMA"), 2,2-bis(4-(meth)acryloyloxyethoxyphenyl)propane, 2,2-bis(4-methacryloyloxypolyethoxyphenyl)propane (having an average added mole number of ethoxy groups of 2.6, commonly known as "D-2.6E"), 2,2-bis(4-(meth)acryloyloxydiethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxytriethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxytetraethoxyphenyl)propane, and 2,2-bis(4-(meth)acryloyloxypentaethoxyphenyl)propane are preferred.
[0046] Examples of the aliphatic compound-based bifunctional monomer include glycerol di(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, butylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,3-butanediol di(meth)acrylate, 1,5-pentanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, 1,2-bis(3-methacryloyloxy-2-hydroxypropoxy)ethane, 2,2,4-trimethylhexamethylenebis(2-carbamoyloxyethyl)di(meth)acrylate, N-methacryloyloxyethylacrylamide, and N-methacryloyloxypropylamide. Among these, triethylene glycol diacrylate, triethylene glycol dimethacrylate (commonly known as "3G"), neopentyl glycol di(meth)acrylate, 1,2-bis(3-methacryloyloxy-2-hydroxypropoxy)ethane, and 2,2,4-trimethylhexamethylene bis(2-carbamoyloxyethyl)dimethacrylate (commonly known as "UDMA") are preferred. In order to exhibit high initial adhesive strength and adhesive durability even to dry tooth tissue, 1,10-decanediol dimethacrylate (commonly known as "DD"), 2,2,4-trimethylhexamethylene bis(2-carbamoyloxyethyl)dimethacrylate, and N-methacryloyloxyethylacrylamide (commonly known as "MAEA") are preferred.
[0047] Examples of trifunctional or higher monomers include trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, trimethylolmethane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, N,N-(2,2,4-trimethylhexamethylene)bis[2-(aminocarboxy)propane-1,3-diol]tetra(meth)acrylate, 1,7-diacryloyloxy-2,2,6,6-tetra(meth)acryloyloxymethyl-4-oxaheptane, etc. Among these, N,N-(2,2,4-trimethylhexamethylene)bis[2-(aminocarboxy)propane-1,3-diol]tetramethacrylate is preferred.
[0048] Among the above hydrophobic monomers (c), from the viewpoint of mechanical strength or handling, aromatic bifunctional monomers and aliphatic bifunctional monomers are preferably used. As aromatic bifunctional monomers, 2,2-bis[4-(3-methacryloyloxy-2-hydroxypropoxy)phenyl]propane and 2,2-bis(4-methacryloyloxypolyethoxyphenyl)propane (average molar number of ethoxy groups added is 2.6) are preferred. As the aliphatic compound-based bifunctional monomer, glycerol di(meth)acrylate, triethylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, 1,2-bis(3-methacryloyloxy-2-hydroxypropoxy)ethane, 2,2,4-trimethylhexamethylenebis(2-carbamoyloxyethyl)dimethacrylate, and N-methacryloyloxyethylacrylamide are preferred.
[0049] Among the above hydrophobic monomers (c), from the viewpoints of initial adhesive strength, adhesive durability, and mechanical strength to wet tooth tissue, Bis-GMA, D-2.6E, 3G, UDMA, DD, and MAEA are more preferred, and Bis-GMA, UDMA, and 3G are even more preferred. From the viewpoint of showing high initial adhesive strength and adhesive durability even to dry tooth tissue, Bis-GMA, D-2.6E, 3G, UDMA, DD, and MAEA are more preferred, and D-2.6E, DD, and MAEA are even more preferred.
[0050] The hydrophobic monomer (c) may be blended alone or in combination of two or more kinds. The content of the hydrophobic monomer (c) is preferably in the range of 9 to 90 parts by mass, more preferably in the range of 15 to 80 parts by mass, and even more preferably in the range of 20 to 75 parts by mass, based on 100 parts by mass of the total amount of the monomers in the non-solvent-based dental adhesive composition (B), from the viewpoint of the permeability of the composition into the tooth structure and the mechanical strength. On the other hand, in order to show high initial adhesive strength, adhesive durability, and dentin cohesive fracture rate even to a tooth structure in a dry state, the content of the hydrophobic monomer (c) is preferably in the range of 40 to 99 parts by mass, more preferably in the range of 60 to 97 parts by mass, and even more preferably in the range of 70 to 95 parts by mass, based on 100 parts by mass of the total amount of the monomers in the non-solvent-based dental adhesive composition (B).
[0051] <Water-soluble photoinitiator system (d)> When the non-solvent-based dental adhesive composition (B) comes into contact with the surface of a tooth (wet body), the water-soluble photopolymerization initiator system (d) dissolves locally on the surface of the tooth or in the water contained in the tooth, and in the area where the water-soluble photopolymerization initiator system (d) has dissolved, the initiator becomes highly concentrated, which has the effect of selectively enhancing the polymerization hardening property at the adhesive interface and inside the resin-impregnated layer.
[0052] The water-soluble photopolymerization initiator system (d) has a solubility in water at 25° C. of 10 g / L or more, preferably 15 g / L or more, more preferably 20 g / L or more, and even more preferably 25 g / L or more. If the solubility is less than 10 g / L, when the non-solvent-based dental adhesive composition (B) of the present invention is applied to a wet body, the water-soluble photopolymerization initiator system (d) does not dissolve sufficiently in the water of the wet body at the adhesive interface, and as a result, the polymerization promotion effect is difficult to exhibit.
[0053] Examples of the water-soluble photopolymerization initiator system (d) include (i) a water-soluble cleavage-type photopolymerization initiator (d-1), (ii) a water-soluble photopolymerization initiator system consisting of a combination of a water-soluble photosensitizer (d-2) having a water solubility of 10 g / L or more at 25° C. and a water-insoluble reducing agent (d-3) having a water solubility of less than 10 g / L at 25° C., (iii) a water-soluble photopolymerization initiator system consisting of a combination of a water-insoluble photosensitizer (d-4) having a water solubility of less than 10 g / L at 25° C. and a water-soluble reducing agent (d-5) having a water solubility of 10 g / L or more at 25° C., and (iv) a water-soluble photopolymerization initiator system consisting of a combination of a water-soluble photosensitizer (d-2) having a water solubility of 10 g / L or more at 25° C. and a water-soluble reducing agent (d-5) having a water solubility of 10 g / L or more at 25° C. These photopolymerization initiators and water-soluble photopolymerization initiator systems can be used alone or in combination of two or more. For example, when the water-soluble photopolymerization initiator system (d) contains a water-soluble cleavage-type photopolymerization initiator (d-1), the polymerization initiator may be only the water-soluble cleavage-type photopolymerization initiator (d-1), or may further contain a water-insoluble reducing agent (d-3) and a water-insoluble photosensitizer (d-4) in addition to the water-soluble cleavage-type photopolymerization initiator (d-1). In the present invention, when the water-soluble photopolymerization initiator system (d) is the water-soluble photopolymerization initiator system of the above (ii) to (iv), it is necessary that at least one of the agents constituting the system has a solubility in water of 10 g / L or more at 25°C. The water-soluble photopolymerization initiator system (d) of the above (ii) to (iv) can exhibit a polymerization promotion effect similar to the above (i) as long as the solubility of at least one agent satisfies the above condition. When the water-soluble photopolymerization initiator system (d) corresponds to the above (ii) to (iv), the "solubility in water at 25°C of 10 g / L or more" of the water-soluble photopolymerization initiator system (d) means that at least one of the agents constituting the system has a solubility in water at 25°C of 10 g / L or more.
[0054] The water-soluble photopolymerization initiator system (d) may be dissolved in the water on the surface of the tooth (wet body) and may selectively enhance the polymerization hardening property at the adhesive interface and inside the resin-impregnated layer, and may be dissolved in the non-solvent-based dental adhesive composition (B) or dispersed in powder form in the composition.
[0055] When the water-soluble photopolymerization initiator system (d) is dispersed in powder form, if the average particle size is too large, it tends to settle, so it is preferably 500 μm or less, more preferably 100 μm or less, and even more preferably 50 μm or less. On the other hand, if the average particle size is too small, the specific surface area of the powder becomes too large, and the amount dispersible in the composition decreases, so it is preferably 0.01 μm or more. That is, the average particle size of the powder of the water-soluble photopolymerization initiator system (d) is preferably in the range of 0.01 to 500 μm, more preferably in the range of 0.01 to 100 μm, and even more preferably in the range of 0.01 to 50 μm.
[0056] When the water-soluble photopolymerization initiator system (d) is dispersed in powder form, the photopolymerization initiator may have various shapes, such as spherical, needle-like, plate-like, and crushed, but is not particularly limited. The water-soluble photopolymerization initiator system (d) can be prepared by a conventionally known method, such as a pulverization method, a freeze-drying method, or a reprecipitation method. For example, it can be obtained by the following method. Method 1: A method of preparing an aqueous solution of the water-soluble photopolymerization initiator system (d), freezing the aqueous solution at -50°C, and then vacuum drying the solution in the frozen state; Method 2: A method of preparing a saturated aqueous solution of the water-soluble photopolymerization initiator system (d), pouring this aqueous solution into ethanol at 0°C, filtering the resulting crystals, washing them with ethanol, and air-drying them; Method 3: A method of preparing a saturated aqueous solution of the water-soluble photoinitiator system (d), rapidly cooling the aqueous solution to 0°C, filtering the resulting crystals, and air-drying the crystals; and Method 4: By mechanical crushing and sieving.
[0057] Among these methods for preparing the water-soluble photopolymerization initiator system (d), the freeze-drying method (Method 1) and the reprecipitation method (Method 2) are preferred, and the freeze-drying method (Method 1) is more preferred, from the viewpoint of the average particle size of the resulting powder.
[0058] The average particle size of the powder of each water-soluble photopolymerization initiator system (d) can be calculated as the volume average particle size after performing image analysis using image analysis software (Mac-View; manufactured by Mountec Co., Ltd.) based on electron micrographs of 100 or more particles.
[0059] The content of the water-soluble photopolymerization initiator system (d) is preferably 0.01 to 20 parts by mass relative to 100 parts by mass of the total amount of monomers in the non-solvent dental adhesive composition (B) from the viewpoint of the curability of the obtained non-solvent dental adhesive composition (B), and is more preferably 0.05 to 10 parts by mass, and even more preferably 0.1 to 5 parts by mass, from the viewpoint of showing higher initial adhesive strength and adhesive durability. If the content of the water-soluble photopolymerization initiator system (d) is 20 parts by mass or less, sufficient adhesive strength is easily obtained even when the polymerization performance of the water-soluble photopolymerization initiator system (d) is low, and furthermore, dissolution, dispersion, and diffusion in the non-solvent dental adhesive composition (B) are easily performed.
[0060] The water-soluble cleavage-type photopolymerization initiator (d-1), the water-soluble photosensitizer (d-2), the water-insoluble reducing agent (d-3), the water-insoluble photosensitizer (d-4), and the water-soluble reducing agent (d-5) are described in detail below.
[0061] Water-soluble cleavage-type photoinitiator (d-1) with a solubility in water of 10 g / L or more at 25°C Examples of the water-soluble cleavage-type photopolymerization initiator (d-1) include water-soluble acylphosphine oxides, water-soluble thioxanthones, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one having a (poly)ethylene glycol chain introduced into the hydroxyl group, 1-hydroxycyclohexyl phenyl ketone having a (poly)ethylene glycol chain introduced into the hydroxyl group and / or phenyl group, and 1-hydroxycyclohexyl phenyl ketone having a -OCH 2 COO - Na + a (poly)ethylene glycol chain is introduced to the hydroxyl group and / or phenyl group of 2-hydroxy-2-methyl-1-phenylpropan-1-one; a -OCH 2 COO - Na + and α-hydroxyalkylacetophenones such as those introduced with 2-methyl-1[4-(methylthio)phenyl]-2-morpholinopropan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone-1, etc., in which the amino group of α-aminoalkylphenones is converted into a quaternary ammonium salt. The water-soluble cleavage-type photopolymerization initiator (d-1) may be used alone or in combination of two or more kinds.
[0062] Examples of the water-soluble acylphosphine oxides include a compound represented by the following general formula (1) and a compound represented by the following general formula (2).
[0063] [ka]
[0064] [ka]
[0065] [In the formula, R 1 , R 2 , R 3 , R 4 , R 5 , and R 6 are each independently a linear or branched alkyl group having 1 to 4 carbon atoms or a halogen atom, and M is a hydrogen ion, an alkali metal ion, an alkaline earth metal ion, a magnesium ion, a pyridinium ion (the pyridine ring may have a substituent), or HN + Z 1 Z 2 Z 3 (In the formula, Z 1 , Z 2 , and Z 3 are each independently an organic group or a hydrogen atom), and n is 1 or 2.
[0066] R 1 , R 2 , R 3 , R 4 , R 5 , and R 6 The alkyl group in is not particularly limited as long as it is a straight or branched alkyl group having 1 to 4 carbon atoms, and examples thereof include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a 2-methylpropyl group, and a tert-butyl group. When M is a pyridinium ion, examples of the substituent on the pyridine ring include a halogen atom (a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom), a carboxy group, a straight or branched acyl group having 2 to 6 carbon atoms, a straight or branched alkyl group having 1 to 6 carbon atoms, and a straight or branched alkoxy group having 1 to 6 carbon atoms. M is an alkali metal ion, an alkaline earth metal ion, a magnesium ion, a pyridinium ion (the pyridine ring may have a substituent), or HN + Z 1 Z2 Z 3 (wherein the symbols have the same meanings as above) is preferred. Examples of the alkali metal ion include a lithium ion, a sodium ion, a potassium ion, a rubidium ion, and a cesium ion. Examples of the alkaline earth metal ion include a calcium ion, a strontium ion, a barium ion, and a radium ion. Z 1 , Z 2 , and Z 3 Examples of the organic group include the same as the substituents on the pyridine ring (excluding halogen atoms).
[0067] Among these, R 1 , R 2 , R 3 , R 4 , R 5 , and R 6 Compounds in which is a methyl group are preferred in terms of storage stability and color stability in the non-solvent dental adhesive composition (B). In addition, examples of the ammonium ion include ammonium ions derived from various amines. Examples of the amine include ammonia, trimethylamine, diethylamine, dimethylaniline, ethylenediamine, triethanolamine, N,N-dimethylaminomethacrylate, N,N-dimethylaminobenzoic acid and its alkyl esters, N,N-diethylaminobenzoic acid and its alkyl esters, and N,N-bis(2-hydroxyethyl)-p-toluidine.
[0068] Among these water-soluble acylphosphine oxides, sodium phenyl(2,4,6-trimethylbenzoyl)phosphinic acid, lithium phenyl(2,4,6-trimethylbenzoyl)phosphinic acid, sodium bis(2,4,6-trimethylbenzoyl)phosphinic acid, and lithium bis(2,4,6-trimethylbenzoyl)phosphinic acid are particularly preferred.
[0069] Water-soluble acylphosphine oxides having such a structure can be synthesized according to known methods, and some of them are also available as commercially available products. For example, they can be synthesized by the methods disclosed in JP-A-57-197289, WO 2014 / 095724, etc.
[0070] Examples of the water-soluble thioxanthones include 2-hydroxy-3-(9-oxo-9H-thioxanthen-4-yloxy)-N,N,N-trimethyl-1-propanaminium chloride, 2-hydroxy-3-(1-methyl-9-oxo-9H-thioxanthen-4-yloxy)-N,N,N-trimethyl-1-propanaminium chloride, 2-hydroxy-3-(9-oxo-9H-thioxanthen-2-yloxy)-N,N,N-trimethyl-1-propanaminium chloride, 2-hydroxy-3-(9-oxo-9H-thioxanthen-2-yloxy)-N,N,N-trimethyl-1-propanaminium chloride, 2- Hydroxy-3-(3,4-dimethyl-9-oxo-9H-thioxanthen-2-yloxy)-N,N,N-trimethyl-1-propanaminium chloride, 2-hydroxy-3-(3,4-dimethyl-9H-thioxanthen-2-yloxy)-N,N,N-trimethyl-1-propanaminium chloride, 2-hydroxy-3-(1,3,4-trimethyl-9-oxo-9H-thioxanthen-2-yloxy)-N,N,N-trimethyl-1-propanaminium chloride, and the like can be used.
[0071] Water-soluble photosensitizer (d-2) Next, the water-soluble photosensitizer (d-2) will be described. In the embodiment in which the water-soluble photopolymerization initiator system (d) in the non-solvent dental adhesive composition (B) of the present invention contains a water-soluble photosensitizer (d-2) having a solubility in water of 10 g / L or more at 25 ° C., it is preferable to use a water-insoluble reducing agent (d-3) having a solubility in water of less than 10 g / L at 25 ° C. and / or a water-soluble reducing agent (d-5) having a solubility in water of 10 g / L or more at 25 ° C. as a polymerization promoter in combination from the viewpoint of showing high initial adhesive strength and adhesive durability to tooth substance. The water-soluble photosensitizer (d-2) having a solubility in water of 10 g / L or more at 25 ° C. is preferably a compound represented by the following general formula (3). The water-soluble photosensitizer (d-2) having a solubility in water of 10 g / L or more at 25 ° C. may be used alone or in combination of two or more.
[0072] [ka] [In the formula, R 8 , R 9 , R 10 , R 11 , R 12 , R 13 , R 14 and R 15 are each independently a hydrogen atom, a linear or branched alkyl group having 1 to 4 carbon atoms, a linear or branched alkoxy group having 1 to 4 carbon atoms, a halogen atom, -OH, or -COOY 1 and R 8 ~R 15 At least one of the following is -COOY 1 and Y 1 represents an organic cation or an inorganic cation.
[0073] R 8 ~R 15 The alkyl group of R is not particularly limited as long as it is a linear or branched alkyl group having 1 to 4 carbon atoms. 1 ~R 6 The alkyl groups are the same as those in the alkyl groups R 8 ~R 15The alkyl group of R is preferably a linear alkyl group having 1 to 3 carbon atoms, more preferably a methyl group or an ethyl group, and further preferably a methyl group. 8 ~R 15 The alkoxy group is not particularly limited as long as it is a straight-chain or branched-chain alkoxy group having 1 to 4 carbon atoms, and examples thereof include a methoxy group, an ethoxy group, an n-propoxy group, an isopropoxy group, an n-butoxy group, a sec-butoxy group, a tert-butoxy group, etc. The alkoxy group is preferably a straight-chain alkoxy group having 1 to 3 carbon atoms, more preferably a methoxy group or an ethoxy group, and even more preferably a methoxy group.
[0074] Y 1 Examples of the cations include an alkali metal ion, an alkaline earth metal ion, a magnesium ion, a pyridinium ion (the pyridine ring may have a substituent), and HN + Z 4 Z 5 Z 6 (In the formula, Z 4 , Z 5 , and Z 6 each independently represents an organic group or a hydrogen atom) is preferred.
[0075] Examples of the alkali metal ions include lithium ions, sodium ions, potassium ions, rubidium ions, and cesium ions. Examples of the alkaline earth metal ions include calcium ions, strontium ions, barium ions, and radium ions. 1 When HN is a pyridinium ion, examples of the substituent on the pyridine ring include a halogen atom (a fluorine atom, a chlorine atom, a bromine atom, an iodine atom), a carboxy group, a linear or branched acyl group having 2 to 6 carbon atoms, a linear or branched alkyl group having 1 to 6 carbon atoms, and a linear or branched alkoxy group having 1 to 6 carbon atoms. + Z 4 Z 5 Z 6Examples of the ammonium ion represented by the formula (I) include those derived from various amines. Examples of the amine include ammonia, trimethylamine, diethylamine, dimethylaniline, ethylenediamine, triethanolamine, N,N-dimethylamino methacrylate, 4-(N,N-dimethylamino)benzoic acid and its alkyl esters, 4-(N,N-diethylamino)benzoic acid and its alkyl esters, and N,N-bis(2-hydroxyethyl)-p-toluidine. 4 , Z 5 , and Z 6 Examples of the organic group of Y include the same as the substituent of the pyridine ring (excluding halogen atoms). 1 Examples include lithium ions, sodium ions, potassium ions, calcium ions, magnesium ions, and HN + Z 4 Z 5 Z 6 Preferred are ammonium ions represented by the formula: embedded image, more preferred are lithium ions, sodium ions, potassium ions, calcium ions and magnesium ions, and even more preferred are lithium ions and sodium ions. For example, Y 1 If is a divalent ion (e.g., calcium ion), then "-COOY 1 " is "-COOCa 1 / 2 " In other words, Y 1 When is a divalent ion, the compound represented by formula (3) forms a dimer.
[0076] The compound represented by the general formula (3) is R 8 ~R 15 At least one of the groups is -COOY 1 Preferred are compounds in which R 8 ~R 15 At least one of the groups is -COOY 1 and R 8 ~R 15 More preferred are compounds in which the remaining groups are hydrogen atoms or methyl groups; 8 ~R 15 At least one of the groups is -COOY 1and R 8 ~R 15 More preferred are compounds in which the remaining groups are hydrogen atoms or methyl groups, and the number of methyl groups is 3 or less; 8 is a hydrogen atom or a methyl group, and R 9 is a methyl group or -COOY 1 and R 10 is a methyl group, and (i) R 9 is a methyl group, R 11 ~R 15 Any one of -COOY 1 and the other four are hydrogen atoms; (ii) R 9 -COOY 1 If R 11 ~R 15 Among these, compounds in which R 8 is a hydrogen atom or a methyl group, and R 9 and R 10 is a methyl group, and R 11 , R 12 , R 13 , and R 14 are all hydrogen atoms, and R 15 COOY 1 The compound represented by the formula (I) is most preferred in terms of adhesion to tooth structure.
[0077] The compound represented by the general formula (3) having such a structure can be synthesized according to a known method.
[0078] Specific examples of the compound represented by general formula (3) include, but are not limited to, those shown below.
[0079] [ka]
[0080] Non-water-soluble reducing agent (d-3) As another embodiment of the water-soluble photopolymerization initiator system (d) of the non-solvent dental adhesive composition (B) of the present invention, when the water-soluble photosensitizer (d-2) is contained, a water-insoluble reducing agent (d-3) may be used as a polymerization accelerator used in combination. Examples of the water-insoluble reducing agent (d-3) include amines, sulfinic acid and its salts, borate compounds, barbituric acid derivatives, triazine compounds, copper compounds, tin compounds, vanadium compounds, halogen compounds, aldehydes, thiol compounds, sulfites, hydrogen sulfites, and thiourea compounds, each of which has a solubility in water of less than 10 g / L at 25° C. The water-insoluble reducing agent (d-3) may be used alone or in combination of two or more kinds.
[0081] The amines used as the non-water-soluble reducing agent (d-3) are divided into aliphatic amines and aromatic amines. Examples of aliphatic amines include primary aliphatic amines such as n-octylamine; secondary aliphatic amines such as dibutylamine; and tertiary aliphatic amines such as N-lauryldiethanolamine, N-ethyldiethanolamine dimethacrylate, triethanolamine dimethacrylate, triethanolamine trimethacrylate, and tributylamine. Among these, tertiary aliphatic amines are preferred from the viewpoint of the curability and storage stability of the composition, and 2-(dimethylamino)ethyl methacrylate is more preferred from the viewpoint of the curability and storage stability of the non-solvent dental adhesive composition (B).
[0082] Examples of aromatic amines include N,N-bis(2-hydroxyethyl)-3,5-dimethylaniline, N,N-bis(2-hydroxyethyl)-p-toluidine, N,N-bis(2-hydroxyethyl)-3,4-dimethylaniline, N,N-bis(2-hydroxyethyl)-4-ethylaniline, N,N-bis(2-hydroxyethyl)-4-isopropylaniline, N,N-bis(2-hydroxyethyl)-4-t-butylaniline, N,N-bis(2-hydroxyethyl)-3,5-di-isopropylaniline, N,N-bis(2-hydroxyethyl)-3,5-di-t-butylaniline, N,N-dimethylaniline, N,N-dimethyl-p-toluidine, and N,N-dimethyl-m-toluidine. dimethylaniline, N,N-diethyl-p-toluidine, N,N-dimethyl-3,5-dimethylaniline, N,N-dimethyl-3,4-dimethylaniline, N,N-dimethyl-4-ethylaniline, N,N-dimethyl-4-isopropylaniline, N,N-dimethyl-4-t-butylaniline, N,N-dimethyl-3,5-di-t-butylaniline, 4-(N,N-dimethylamino)ethyl benzoate, 4-(N,N-dimethylamino)methyl benzoate, 4-(N,N-dimethylamino)n-butoxyethyl benzoate, 4-(N,N-dimethylamino)2-(methacryloyloxy)ethyl benzoate, 4-(N,N-dimethylamino)benzophenone, and 4-(N,N-dimethylamino)butyl benzoate. Among these, at least one selected from the group consisting of ethyl 4-(N,N-dimethylamino)benzoate, n-butoxyethyl 4-(N,N-dimethylamino)benzoate, and 4-(N,N-dimethylamino)benzophenone is preferably used from the viewpoint of imparting excellent curing properties to the non-solvent-based dental adhesive composition (B).
[0083] Specific examples of sulfinic acid and its salts, borate compounds, barbituric acid derivatives, triazine compounds, copper compounds, tin compounds, vanadium compounds, halogen compounds, aldehydes, thiol compounds, sulfites, hydrogen sulfites, and thiourea compounds include those described in WO 2008 / 087977.
[0084] Non-water-soluble photosensitizer (d-4) As another embodiment of the water-soluble photopolymerization initiator system (d) of the non-solvent dental adhesive composition (B) of the present invention, when the water-soluble reducing agent (d-5) is contained, a water-insoluble photosensitizer (d-4) may be used as a photopolymerization initiator used in combination. Examples of the water-insoluble photosensitizer (d-4) include thioxanthones, ketals, α-diketones, coumarins, anthraquinones, benzoin alkyl ether compounds, α-aminoketone compounds, etc., which have a solubility in water of less than 10 g / L at 25° C. The water-insoluble photosensitizer (d-4) may be used alone or in combination of two or more kinds. The photoreaction between the photosensitizer and the reducing agent involves complex hydrogen abstraction reactions and other reactions, and there are still some points that remain unclear; however, since radicals are generated in both the photosensitizer and the reducing agent, the fact that either or both of the photosensitizer and the reducing agent are water-soluble brings about the effects of the present invention in an adhesive dental material kit comprising a dental cleaning material (A) and a non-solvent-based dental adhesive composition (B).
[0085] Examples of the thioxanthones include thioxanthone, 2-chlorothioxanthen-9-one, and the like.
[0086] Examples of the ketals include benzyl dimethyl ketal and benzyl diethyl ketal.
[0087] Examples of the α-diketones include diacetyl, benzil, camphorquinone, 2,3-pentadione, 2,3-octadione, 9,10-phenanthrenequinone, 4,4′-oxybenzil, acenaphthenequinone, etc. Among these, camphorquinone is particularly preferred from the viewpoint of having a maximum absorption wavelength in the visible light region.
[0088] Examples of the coumarin compound include 3,3'-carbonylbis(7-diethylaminocoumarin), 3-(4-methoxybenzoyl)coumarin, 3-thienoylcoumarin, 3-benzoyl-5,7-dimethoxycoumarin, 3-benzoyl-7-methoxycoumarin, 3-benzoyl-6-methoxycoumarin, 3-benzoyl-8-methoxycoumarin, 3-benzoylcoumarin, 7-methoxy-3-(p-nitrobenzoyl)coumarin, 3-(p-nitrobenzoyl)coumarin, 3,5-carbonylbis(7-methoxycoumarin), 3-benzoyl-6-bromo Coumarin, 3,3'-carbonylbiscoumarin, 3-benzoyl-7-dimethylaminocoumarin, 3-benzoylbenzo[f]coumarin, 3-carboxycoumarin, 3-carboxy-7-methoxycoumarin, 3-ethoxycarbonyl-6-methoxycoumarin, 3-ethoxycarbonyl-8-methoxycoumarin, 3-acetylbenzo[f]coumarin, 3-benzoyl-6-nitrocoumarin, 3-benzoyl-7-diethylaminocoumarin, 7-dimethylamino-3-(4-methoxybenzoyl)coumarin, 7-diethylamino-3-(4-methoxybenzoyl)coumarin coumarin, 7-diethylamino-3-(4-diethylamino)coumarin, 7-methoxy-3-(4-methoxybenzoyl)coumarin, 3-(4-nitrobenzoyl)benzo[f]coumarin, 3-(4-ethoxycinnamoyl)-7-methoxycoumarin, 3-(4-dimethylaminocinnamoyl)coumarin, 3-(4-diphenylaminocinnamoyl)coumarin, 3-[(3-dimethylbenzothiazol-2-ylidene)acetyl]coumarin, 3-[(1-methylnaphtho[1,2-d]thiazol-2-ylidene)acetyl]coumarin, 3,3'-carbo nylbis(6-methoxycoumarin), 3,3'-carbonylbis(7-acetoxycoumarin), 3,3'-carbonylbis(7-dimethylaminocoumarin), 3-(2-benzothiazolyl)-7-(diethylamino)coumarin, 3-(2-benzothiazolyl)-7-(dibutylamino)coumarin, 3-(2-benzimidazolyl)-7-(diethylamino)coumarin, 3-(2-benzothiazolyl)-7-(dioctylamino)coumarin, 3-acetyl-7-(dimethylamino)coumarin, 3,3'-carbonylbis(7-dibutylamino)coumarin, 3,Examples of the compounds include those described in JP-A-9-3109 and JP-A-10-245525, such as 3'-carbonyl-7-diethylaminocoumarin-7'-bis(butoxyethyl)aminocoumarin, 10-[3-[4-(dimethylamino)phenyl]-1-oxo-2-propenyl]-2,3,6,7-tetrahydro-1,1,7,7-tetramethyl-1H,5H,11H-[1]benzopyrano[6,7,8-ij]quinolizin-11-one, and 10-(2-benzothiazolyl)-2,3,6,7-tetrahydro-1,1,7,7-tetramethyl-1H,5H,11H-[1]benzopyrano[6,7,8-ij]quinolizin-11-one.
[0089] Among the above-mentioned coumarin compounds, 3,3'-carbonylbis(7-diethylaminocoumarin) and 3,3'-carbonylbis(7-dibutylaminocoumarin) are particularly preferred.
[0090] Examples of the anthraquinones include anthraquinone, 1-chloroanthraquinone, 2-chloroanthraquinone, 1-bromoanthraquinone, 1,2-benzanthraquinone, 1-methylanthraquinone, 2-ethylanthraquinone, and 1-hydroxyanthraquinone.
[0091] Examples of the benzoin alkyl ether compound include benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzoin isobutyl ether.
[0092] Examples of the α-aminoketone compounds include 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one.
[0093] Among these water-insoluble photosensitizers (d-4), it is preferable to use at least one selected from the group consisting of α-diketones and coumarin compounds.
[0094] Water-soluble reducing agent (d-5) As another embodiment of the water-soluble photopolymerization initiator system (d) of the non-solvent dental adhesive composition (B) of the present invention, when the water-soluble photosensitizer (d-2) and / or the non-water-soluble photosensitizer (d-4) are contained, a water-soluble reducing agent (d-5) is used as a polymerization accelerator used in combination. Examples of the water-soluble reducing agent (d-5) include amines, sulfinic acid and its salts, borate compounds, barbituric acid derivatives, triazine compounds, copper compounds, tin compounds, vanadium compounds, halogen compounds, aldehydes, thiol compounds, sulfites, hydrogen sulfites, and thiourea compounds, each of which has a solubility in water of 10 g / L or more at 25° C.
[0095] Among the water-soluble reducing agents (d-5), it is particularly preferable to use the compound (d-5a) represented by general formula (4) because it exhibits high adhesiveness to dentin. [ka] [In the formula, R 16 and R 17 are each independently a linear or branched alkyl group having 1 to 4 carbon atoms; R 18 , R 19 , R 20 , R 21 and R 22 are each independently a hydrogen atom, a linear or branched alkyl group having 1 to 4 carbon atoms, a linear or branched alkoxy group having 1 to 4 carbon atoms, a halogen atom, -OH, -COOH, or -COOY 2 and R 18 ~R 22 At least one of the groups is -COOH or -COOY. 2 and Y 2 represents an organic cation or an inorganic cation.
[0096] R 16 ~R 22The alkyl group of R is not particularly limited as long as it is a straight-chain or branched-chain alkyl group having 1 to 4 carbon atoms, and examples thereof include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a 2-methylpropyl group, and a tert-butyl group. The alkyl group is preferably a straight-chain alkyl group having 1 to 3 carbon atoms, more preferably a methyl group or an ethyl group, and even more preferably a methyl group. 18 ~R 22 The alkoxy group is not particularly limited as long as it is a straight-chain or branched-chain alkoxy group having 1 to 4 carbon atoms, and examples thereof include a methoxy group, an ethoxy group, an n-propoxy group, an isopropoxy group, an n-butoxy group, a sec-butoxy group, a tert-butoxy group, etc. The alkoxy group is preferably a straight-chain alkoxy group having 1 to 3 carbon atoms, more preferably a methoxy group or an ethoxy group, and even more preferably a methoxy group.
[0097] Y 2 Examples of the cations include an alkali metal ion, an alkaline earth metal ion, a magnesium ion, a pyridinium ion (the pyridine ring may have a substituent), and HN + Z 7 Z 8 Z 9 (In the formula, Z 7 , Z 8 , and Z 9 are each independently an organic group or a hydrogen atom), an ammonium ion represented by the formula (I).
[0098] Examples of the alkali metal ions include lithium ions, sodium ions, potassium ions, rubidium ions, and cesium ions. Examples of the alkaline earth metal ions include calcium ions, strontium ions, barium ions, and radium ions. 2 When HN is a pyridinium ion, examples of the substituent on the pyridine ring include a halogen atom (a fluorine atom, a chlorine atom, a bromine atom, an iodine atom), a carboxy group, a linear or branched acyl group having 2 to 6 carbon atoms, a linear or branched alkyl group having 1 to 6 carbon atoms, and a linear or branched alkoxy group having 1 to 6 carbon atoms. + Z7 Z 8 Z 9 Examples of the ammonium ion represented by the formula (I) include those derived from various amines. Examples of the amine include ammonia, trimethylamine, diethylamine, dimethylaniline, ethylenediamine, triethanolamine, N,N-dimethylamino methacrylate, 4-(N,N-dimethylamino)benzoic acid and its alkyl esters, 4-(N,N-diethylamino)benzoic acid and its alkyl esters, and N,N-bis(2-hydroxyethyl)-p-toluidine. 7 , Z 8 , and Z 9 Examples of the organic group of Y include the same as the substituent of the pyridine ring (excluding halogen atoms). 2 Examples include lithium ions, sodium ions, potassium ions, calcium ions, magnesium ions, and HN + Z 7 Z 8 Z 9 Preferred are ammonium ions represented by the formula: embedded image, more preferred are lithium ions, sodium ions, potassium ions, calcium ions and magnesium ions, and even more preferred are lithium ions and sodium ions. For example, Y 2 If is a divalent ion (e.g., calcium ion), then "-COOY 2 " is "-COOCa 1 / 2 " In other words, Y 2 When is a divalent ion, compound (d-5a) represented by general formula (4) forms a dimer.
[0099] The compound (d-5a) represented by the general formula (4) is R 16 and R 17 is a methyl group or an ethyl group, and R 18 ~R 22 At least one of the groups is -COOH or -COOY 2 Preferred are compounds in which R 16 and R 17 is a methyl group or an ethyl group, and R 18 ~R 22At least one of the groups is -COOH or -COOY 2 and R 18 ~R 22 More preferred are compounds in which at least one of the remaining groups is -OH or a linear alkoxy group having 1 to 3 carbon atoms; 16 and R 17 is a methyl group, and R 18 and R 19 Either one of them is -COOH or -COOY 2 and R 20 ~R 22 More preferred is a compound in which at least one of the groups is -OH or a methoxy group; 16 and R 17 is a methyl group, and R 18 and R 19 Either one of them is -COOH or -COOY 2 and (i) R 18 -COOH or -COOY 2 If R 19 , R 21 , and R 22 is a hydrogen atom, and R 20 is -OH or a methoxy group, and (ii) R 19 -COOH or -COOY 2 If R 18 , R 20 , and R 22 is a hydrogen atom, and R 21 Particularly preferred are compounds in which R is -OH or a methoxy group. 16 and R 17 is a methyl group, and R 18 -COOH or -COOY 2 and R 19 , R 21 , and R 22 is a hydrogen atom, and R 20 When is a methoxy group, this is most preferred from the standpoint of adhesion to tooth structure.
[0100] Compound (d-5a) having such a structure and represented by general formula (4) can be synthesized according to known methods, and some of them are also available as commercial products.
[0101] Specific examples of the compound (d-5a) represented by general formula (4) include, but are not limited to, those shown below.
[0102] [ka]
[0103] <Hydrophilic monomer (e) having no acidic group> The hydrophilic monomer (e) having no acidic group (hereinafter sometimes simply referred to as "hydrophilic monomer (e)") is preferably a radical monomer having no acidic group and a polymerizable group, and from the viewpoint of ease of radical polymerization, the polymerizable group is more preferably a (meth)acrylic group and / or a (meth)acrylamide group. The hydrophilic monomer (e) having no acidic group means a monomer having a solubility in water of 10 g / L or more at 25°C, preferably a monomer having a solubility of 30 g / L or more, and more preferably a monomer that can be dissolved in water at any ratio at 25°C. The hydrophilic monomer (e) promotes the penetration of the components of the non-solvent-based dental adhesive composition (B) into the tooth tissue, and also penetrates into the tooth tissue itself to adhere to the organic components (collagen) in the tooth tissue. As the hydrophilic monomer (e), those having a hydrophilic group such as a hydroxyl group, an oxymethylene group, an oxyethylene group, an oxypropylene group, or an amide group are preferable, and examples thereof include 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 1,3-dihydroxypropyl (meth)acrylate, 2,3-dihydroxypropyl (meth)acrylate, 2-((meth)acryloyloxy)ethyltrimethylammonium chloride, and polyethylene glycol di(meth)acrylate (having 9 or more oxyethylene groups). hydrophilic monofunctional (meth)acrylate monomers such as N-methylol (meth)acrylamide, N-hydroxyethyl (meth)acrylamide, N,N-bis(2-hydroxyethyl) (meth)acrylamide, N-methoxymethyl (meth)acrylamide, N-ethoxymethyl (meth)acrylamide, diacetone (meth)acrylamide, 4-(meth)acryloylmorpholine, N-trihydroxymethyl-N-methyl (meth)acrylamide, and monofunctional (meth)acrylamide monomers represented by the following general formula (5):
[0104] [ka] [In formula (5), R 23 and R 24are each independently a linear or branched alkyl group having 1 to 3 carbon atoms which may have a substituent, and R 25 is a hydrogen atom or a methyl group.
[0105] R 23 and R 24 As the substituent in R, the same substituent as in general formula (1) can be used. 23 and R 24 In the above formula, examples of the alkyl group having 1 to 3 carbon atoms include a methyl group, an ethyl group, an n-propyl group, and an isopropyl group.
[0106] Among the above hydrophilic monomers (e), from the viewpoint of adhesion to tooth structure, 2-hydroxyethyl (meth)acrylate, 2,3-dihydroxypropyl (meth)acrylate, diacetone (meth)acrylamide and hydrophilic monofunctional (meth)acrylamide monomers are preferred, and 2-hydroxyethyl (meth)acrylate and monofunctional (meth)acrylamide monomers represented by general formula (5) are more preferred. The hydrophilic monomers (e) may be blended alone or in combination of two or more.
[0107] Furthermore, among the monofunctional (meth)acrylamide monomers represented by the general formula (5), from the viewpoint of storage stability, N,N-dimethylacrylamide and N,N-diethylacrylamide are more preferable, and N,N-diethylacrylamide is even more preferable.
[0108] By including the hydrophilic monomer (e) in the non-solvent dental adhesive composition (B), further improvement in adhesive strength can be expected, but if it is excessive, mechanical strength may decrease. Therefore, the content of the hydrophilic monomer (e) is preferably in the range of 9 to 90 parts by mass, more preferably in the range of 15 to 80 parts by mass, and even more preferably in the range of 20 to 75 parts by mass, based on 100 parts by mass of the total amount of the monomers in the non-solvent dental adhesive composition (B). On the other hand, in order to show high initial adhesive strength, adhesive durability, and dentin cohesive fracture rate even to a tooth in a dry state, the content of the hydrophilic monomer (e) is preferably in the range of 0 to 50 parts by mass, more preferably in the range of 0 to 20 parts by mass, and even more preferably in the range of 0 to 10 parts by mass, based on 100 parts by mass of the total amount of the monomers in the non-solvent dental adhesive composition (B). The content of the hydrophilic monomer (e) may be 0 parts by mass.
[0109] In the non-solvent-based dental adhesive composition (B) of the present invention, from the viewpoint of exhibiting high initial adhesive strength, adhesive durability, and dentin cohesive fracture rate even to a tooth in a dry state, the content of the hydrophilic monomer (e) relative to the total mass of the hydrophobic monomer (c) and the hydrophilic monomer (e) is preferably 50% by mass or less, more preferably 40% by mass or less, even more preferably 30% by mass or less, and particularly preferably 20% by mass or less. The content of the hydrophilic monomer (e) may be 0% by mass.
[0110] When the non-solvent dental adhesive composition (B) of the present invention is a composition containing a larger amount of hydrophobic monomer (c) than hydrophilic monomer (e), the reason why it shows high initial adhesive strength and adhesive durability to dentin regardless of the state of the tooth surface (wet or dry state) is not clear, but is presumed as follows. Since the water-soluble photopolymerization initiator system (d) is water-soluble, it has poor solubility in a composition containing a large amount of hydrophobic monomer (c). As a result, when the non-solvent dental adhesive composition (B) of the present invention contacts the tooth substance (wet or dry state), the water-soluble photopolymerization initiator system (d) moves to the tooth substance side where it is more soluble, penetrates into the tooth substance, and hardens. As a result, it is considered that the non-solvent dental adhesive composition (B) of the present invention has high initial adhesive strength and adhesive durability even to the tooth substance in a dry state.
[0111] However, if the content of hydrophobic monomer (c) is too high, the composition may not be able to penetrate into the tooth structure, resulting in a reduced adhesive strength, whereas if the content is too low, the effect of improving mechanical strength may not be fully achieved.
[0112] The non-solvent based dental adhesive composition (B) of the present invention may also contain a non-water soluble photoinitiator system (f).
[0113] <Non-water-soluble photoinitiator system (f)> From the viewpoint of curability, the non-solvent-based dental adhesive composition (B) of the present invention may contain a non-water-soluble photopolymerization initiator system (f) having a solubility in water of less than 10 g / L at 25° C. (hereinafter, simply referred to as "non-water-soluble photopolymerization initiator system (f)") in addition to the water-soluble photopolymerization initiator system (d). A known non-water-soluble photopolymerization initiator can be used as the non-water-soluble photopolymerization initiator system (f). The non-water-soluble photopolymerization initiator system (f) may be formulated as a single type or as a combination of two or more types.
[0114] Examples of the non-water-soluble photopolymerization initiator system (f) include non-water-soluble photopolymerization initiators (f-1) such as (bis)acylphosphine oxides, α-diketones, and coumarin compounds other than the water-soluble cleavage-type photopolymerization initiator (d-1); a non-water-soluble photopolymerization initiator system (f-2) consisting of a combination of a non-water-soluble reducing agent (d-3) having a solubility in water of less than 10 g / L at 25° C. and a non-water-soluble photosensitizer (d-4) having a solubility in water of less than 10 g / L at 25° C. One preferred embodiment includes an adhesive dental material kit comprising a dental cleaning material (A) and a non-solvent-based dental adhesive composition (B), the non-solvent-based dental adhesive composition (B) including a water-soluble photopolymerization initiator system (d) including a monomer (b) having an acidic group, a hydrophobic monomer (c) not having an acidic group, and a water-soluble cleavage-type photopolymerization initiator (d-1), and the non-water-soluble photopolymerization initiator system (f). In the non-solvent-based dental adhesive composition (B), when the water-soluble photopolymerization initiator systems (ii) to (iv) above are used as the water-soluble photopolymerization initiator system (d), the composition may not contain the water-soluble photopolymerization initiator system (f-1) and / or the water-soluble photopolymerization initiator system (f-2) consisting of a combination of a water-soluble photopolymerization initiator (f-3) and a water-soluble photosensitizer (d-4), if necessary.
[0115] Among the (bis)acylphosphine oxides, examples of the acylphosphine oxides include 2,4,6-trimethylbenzoyldiphenylphosphine oxide, 2,6-dimethoxybenzoyldiphenylphosphine oxide, 2,6-dichlorobenzoyldiphenylphosphine oxide, 2,4,6-trimethylbenzoylmethoxyphenylphosphine oxide, 2,4,6-trimethylbenzoylethoxyphenylphosphine oxide, 2,3,5,6-tetramethylbenzoyldiphenylphosphine oxide, and benzoyldi(2,6-dimethylphenyl)phosphonate. Examples of the bisacylphosphine oxides include bis(2,6-dichlorobenzoyl)phenylphosphine oxide, bis(2,6-dichlorobenzoyl)-2,5-dimethylphenylphosphine oxide, bis(2,6-dichlorobenzoyl)-4-propylphenylphosphine oxide, bis(2,6-dichlorobenzoyl)-1-naphthylphosphine oxide, bis(2,6-dimethoxybenzoyl)phenylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,5-dimethylphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, and bis(2,5,6-trimethylbenzoyl)-2,4,4-trimethylpentylphosphine oxide.
[0116] Among these water-insoluble photopolymerization initiators (f-1), it is preferable to use at least one selected from the group consisting of (bis)acylphosphine oxides, α-diketones, and coumarin compounds. This makes it possible to obtain a solvent-free dental adhesive composition (B) that is excellent in photocurability in the visible and near-ultraviolet regions and shows sufficient photocurability even when using any of the light sources, such as a halogen lamp, a light-emitting diode (LED), and a xenon lamp.
[0117] The content of the water-insoluble photopolymerization initiator system (f) is not particularly limited, but from the viewpoint of the curability of the obtained composition, the content of the water-insoluble photopolymerization initiator system (f) is preferably in the range of 0.01 to 10 mass%, more preferably in the range of 0.05 to 7 mass%, and even more preferably in the range of 0.1 to 5 mass%, based on 100 mass parts of the total amount of the monomers in the non-solvent dental adhesive composition (B). When the content of the water-insoluble photopolymerization initiator system (f) is 10 mass% or less, sufficient adhesive strength is easily obtained even when the polymerization performance of the water-insoluble photopolymerization initiator system (f) itself is low, and further, precipitation of the water-insoluble photopolymerization initiator system (f) itself from the non-solvent dental adhesive composition (B) can be suppressed.
[0118] The mass ratio [(d):(f)] of the water-soluble photopolymerization initiator system (d) to the water-insoluble photopolymerization initiator system (f) in the present invention is preferably 10:1 to 1:10, more preferably 7:1 to 1:7, even more preferably 5:1 to 1:5, and particularly preferably 3:1 to 1:3. When the water-soluble photopolymerization initiator system (d) does not exceed a mass ratio of 10:1, the non-solvent dental adhesive composition (B) itself has excellent curing properties, and can exhibit high initial adhesive strength, adhesive durability, and dentin cohesive fracture rate. On the other hand, when the water-insoluble photopolymerization initiator system (f) does not exceed a mass ratio of 1:10, the curing properties of the non-solvent dental adhesive composition (B) itself are enhanced, and polymerization promotion at the adhesive interface also proceeds sufficiently, allowing high initial adhesive strength and adhesive durability to be exhibited.
[0119] <Chemical polymerization initiator> The non-solvent dental adhesive composition (B) of the present invention may further contain a chemical polymerization initiator, and an organic peroxide is preferably used. The organic peroxide used as the above-mentioned chemical polymerization initiator is not particularly limited, and known organic peroxides can be used. Representative organic peroxides include, for example, ketone peroxides, hydroperoxides, diacyl peroxides, dialkyl peroxides, peroxyketals, peroxyesters, and peroxydicarbonates. Specific examples of these organic peroxides include those described in International Publication No. 2008 / 087977.
[0120] In some embodiments, the non-solvent based dental adhesive composition (B) of the present invention preferably further contains a filler (g).
[0121] <Filler (g)> The filler (g) is generally roughly classified into an inorganic filler, an organic-inorganic composite filler, and an organic filler. The filler (g) may be used alone or in combination of two or more kinds.
[0122] Examples of inorganic filler materials include quartz, silica, alumina, silica-titania, silica-titania-barium oxide, silica-zirconia, silica-alumina, lanthanum glass, borosilicate glass, soda glass, barium glass, strontium glass, glass ceramic, aluminosilicate glass, barium boroaluminosilicate glass, strontium boroaluminosilicate glass, fluoroaluminosilicate glass, calcium fluoroaluminosilicate glass, strontium fluoroaluminosilicate glass, barium fluoroaluminosilicate glass, strontium calcium fluoroaluminosilicate glass, ytterbium oxide, silica-coated ytterbium fluoride, etc. These may also be used alone or in combination of two or more. From the viewpoint of the handling property and mechanical strength of the non-solvent-based dental adhesive composition (B), the average particle size of the inorganic filler is preferably 0.001 to 50 μm, more preferably 0.001 to 10 μm. In this specification, the average particle size of the filler means the average particle size of the primary particles of the filler (average primary particle size). In this specification, when the inorganic filler is surface-treated as described later, the average particle size of the inorganic filler means the average particle size before the surface treatment.
[0123] The shape of the inorganic filler is not particularly limited, and the particle size of the filler can be appropriately selected and used, and examples thereof include amorphous fillers and spherical fillers. From the viewpoint of improving the mechanical strength of the non-solvent dental adhesive composition (B), it is preferable to use a spherical filler as the inorganic filler. Here, the spherical filler is a filler in which the particles observed in a unit field of view of a filler photographed with a scanning electron microscope (hereinafter abbreviated as SEM) are rounded, and the average uniformity obtained by dividing the particle diameter in a direction perpendicular to the maximum diameter by the maximum diameter is 0.6 or more. The average particle diameter of the spherical filler is preferably 0.1 μm or more from the viewpoint that the filling rate of the spherical filler in the non-solvent dental adhesive composition (B) is not reduced and the mechanical strength can be maintained, and is preferably 5 μm or less from the viewpoint that the surface area of the spherical filler is sufficient to maintain the mechanical strength of the resulting cured product.
[0124] In order to adjust the fluidity of the non-solvent dental adhesive composition (B), the inorganic filler may be surface-treated in advance with a known surface treatment agent such as a silane coupling agent, if necessary. For example, the hydroxyl groups present on the surface of the inorganic filler can be surface-treated with a silane coupling agent to obtain an inorganic filler with the hydroxyl groups surface-treated. Examples of the surface treatment agent include vinyltrimethoxysilane, vinyltriethoxysilane, vinyltrichlorosilane, vinyltri(β-methoxyethoxy)silane, γ-methacryloyloxypropyltrimethoxysilane, 8-methacryloyloxyoctyltrimethoxysilane, 11-methacryloyloxyundecyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-mercaptopropyltrimethoxysilane, and γ-aminopropyltriethoxysilane.
[0125] The surface treatment method can be any known method without any particular limitation, for example, a method of spraying the above-mentioned surface treatment agent while vigorously stirring the inorganic filler, a method of dispersing or dissolving the inorganic filler and the above-mentioned surface treatment agent in a suitable solvent and then removing the solvent, or a method of hydrolyzing the alkoxy group of the above-mentioned surface treatment agent in an aqueous solution with an acid catalyst to convert it to a silanol group, attaching it to the inorganic filler surface in the aqueous solution, and then removing the water, etc. In any of these methods, the reaction between the inorganic filler surface and the above-mentioned surface treatment agent can be completed by heating in the range of 50 to 150 ° C., and the surface treatment can be performed. The amount of the surface treatment is not particularly limited, and for example, 1 to 10 parts by mass of the surface treatment agent can be used for 100 parts by mass of the inorganic filler before treatment.
[0126] The organic-inorganic composite filler used in the present invention is obtained by adding a monomer compound to the inorganic filler described above in advance, forming a paste, polymerizing it, and pulverizing it. As the organic-inorganic composite filler, for example, TMPT filler (trimethylolpropane methacrylate and silica filler are mixed, polymerized, and pulverized) can be used. The shape of the organic-inorganic composite filler is not particularly limited, and the particle size of the filler can be appropriately selected and used. From the viewpoint of the handleability and mechanical strength of the non-solvent-based dental adhesive composition (B), the average particle size of the organic-inorganic composite filler is preferably 0.001 to 50 μm, more preferably 0.001 to 10 μm.
[0127] Examples of the organic filler material include polymethyl methacrylate, polyethyl methacrylate, methyl methacrylate-ethyl methacrylate copolymer, crosslinked polymethyl methacrylate, crosslinked polyethyl methacrylate, polyamide, polyvinyl chloride, polystyrene, chloroprene rubber, nitrile rubber, ethylene-vinyl acetate copolymer, styrene-butadiene copolymer, acrylonitrile-styrene copolymer, acrylonitrile-styrene-butadiene copolymer, etc., which can be used alone or as a mixture of two or more. The shape of the organic filler is not particularly limited, and the particle size of the filler can be appropriately selected and used. From the viewpoint of the handleability and mechanical strength of the non-solvent dental adhesive composition (B), the average particle size of the organic filler is preferably 0.001 to 50 μm, more preferably 0.001 to 10 μm.
[0128] In this specification, the average particle size of the filler (g) can be determined by a laser diffraction scattering method or by observing the particles with an electron microscope. Specifically, the laser diffraction scattering method is convenient for measuring the particle size of particles of 0.1 μm or more, and the electron microscope observation is convenient for measuring the particle size of ultrafine particles of less than 0.1 μm. 0.1 μm is a value measured by the laser diffraction scattering method.
[0129] Specifically, the laser diffraction scattering method can be performed by, for example, using a laser diffraction particle size distribution analyzer (SALD-2300, manufactured by Shimadzu Corporation) and measuring on a volume basis using a 0.2% aqueous solution of sodium hexametaphosphate as a dispersion medium.
[0130] Specifically, electron microscope observation can be performed by taking a photograph of the particles with a scanning electron microscope (S-4000 model, manufactured by Hitachi, Ltd.) and measuring the particle diameters of particles (200 or more) observed within a unit field of view of the photograph using image analysis type particle size distribution measurement software (Mac-View (manufactured by Mountec Co., Ltd.)). At this time, the particle diameter of the particles is determined as the arithmetic mean value of the longest and shortest lengths of the particles, and the average primary particle diameter is calculated from the number of particles and their particle diameters.
[0131] In the present invention, two or more kinds of fillers having different materials, particle size distributions, and shapes may be mixed or combined and used, and particles other than the filler (g) may be unintentionally contained as impurities within a range that does not impair the effects of the present invention. Commercially available products may be used as the filler in the present invention.
[0132] The content of the filler (g) used in the non-solvent dental adhesive composition (B) is not particularly limited, and the filler (g) is preferably 0 to 2000 parts by mass in 100 parts by mass of the total amount of the monomers in the non-solvent dental adhesive composition (B). The preferred content of the filler (g) varies greatly depending on the embodiment in which it is used, and therefore the preferred content of the filler (g) according to each embodiment will be shown together with the description of the specific embodiment of the non-solvent dental adhesive composition (B) of the present invention described later.
[0133] <Fluoride ion releasing substances> The non-solvent dental adhesive composition (B) may further contain a fluoride ion releasing substance. By blending a fluoride ion releasing substance, a non-solvent dental adhesive composition (B) capable of imparting acid resistance to tooth structure can be obtained. Examples of such fluoride ion releasing substances include metal fluorides such as sodium fluoride, potassium fluoride, sodium monofluorophosphate, lithium fluoride, and ytterbium fluoride. The above fluoride ion releasing substances may be blended alone or in combination of two or more.
[0134] In addition, the non-solvent dental adhesive composition (B) may contain, within the range that does not impair the effects of the present invention, pH adjusters such as N-methyldiethanolamine and triethanolamine, polymerization inhibitors, thickeners, colorants (dyes, pigments), fluorescent agents, fragrances, etc. Also, antibacterial substances such as cetylpyridinium chloride, benzalkonium chloride, (meth)acryloyloxydodecylpyridinium bromide, (meth)acryloyloxyhexadecylpyridinium chloride, (meth)acryloyloxydecylammonium chloride, and triclosan may be contained.
[0135] The non-solvent dental adhesive composition (B) of the present invention can be used, for example, as a dental bonding material, a self-adhesive dental composite resin, a dental cement, a pit and fissure sealant, a loose tooth fixing material, an orthodontic adhesive, etc., and is preferably used as a dental bonding material, a self-adhesive dental composite resin, or a dental cement. In this case, the non-solvent dental adhesive composition (B) of the present invention may be used as a two-part type in which the components are divided into two. The following is a specific embodiment of the application of the non-solvent dental adhesive composition (B).
[0136] <Dental bonding material> In the present invention, the non-solvent dental adhesive composition (B) is used as a dental bonding material in one preferred embodiment. The dental bonding material is a bonding material that can perform the demineralization step, the penetration step, and the curing step in one step and does not substantially contain water or an organic solvent. The dental bonding material may be a two-component type in which two separate components, A and B, are mixed together just before use, or a one-component type in which one component can be used as is. Among them, the one-component type has a greater advantage in use because the process is more simplified. The non-solvent dental adhesive composition (B) used for the dental bonding material is preferably a composition containing a monomer having an acidic group (b), a hydrophobic monomer not having an acidic group (c), a hydrophilic monomer not having an acidic group (e), a water-soluble photopolymerization initiator system (d), a non-water-soluble photopolymerization initiator system (f), and a filler (g).
[0137] The content of each component in the dental bonding material preferably includes 1 to 90 parts by mass of monomer (b) having an acidic group, 1 to 90 parts by mass of hydrophobic monomer (c) not having an acidic group, and 0 to 90 parts by mass of hydrophilic monomer (e) not having an acidic group, per 100 parts by mass of the total amount of monomers in the non-solvent-based dental adhesive composition (B), and more preferably includes 5 to 80 parts by mass of monomer (b) having an acidic group, 5 to 80 parts by mass of hydrophobic monomer (c) not having an acidic group, and 1 to 80 parts by mass of hydrophilic monomer (e) not having an acidic group. Furthermore, relative to 100 parts by mass of the total amount of the monomers, it preferably contains 0.001 to 30 parts by mass of a water-soluble photopolymerization initiator system (d), 0.001 to 30 parts by mass of a non-water-soluble photopolymerization initiator system (f), and 0 to 100 parts by mass of a filler (g), and it is more preferable that it contains 0.05 to 10 parts by mass of the water-soluble photopolymerization initiator system (d), 0.05 to 10 parts by mass of the non-water-soluble photopolymerization initiator system (f), and 1 to 50 parts by mass of a filler (g). On the other hand, in order to exhibit high initial adhesive strength and adhesive durability even to tooth tissue in a dry state, the non-solvent-based dental adhesive composition (B) preferably contains 1 to 90 parts by mass of a monomer (b) having an acidic group, 1 to 99 parts by mass of a hydrophobic monomer (c) not having an acidic group, and 0 to 90 parts by mass of a hydrophilic monomer (e) not having an acidic group, per 100 parts by mass of the total amount of monomers, more preferably contains 1 to 80 parts by mass of a monomer (b) having an acidic group, 10 to 99 parts by mass of a hydrophobic monomer (c) not having an acidic group, and 0 to 80 parts by mass of a hydrophilic monomer (e) not having an acidic group, and even more preferably contains 1 to 80 parts by mass of a monomer (b) having an acidic group, 10 to 99 parts by mass of a hydrophobic monomer (c) not having an acidic group, and 0 to 50 parts by mass of a hydrophilic monomer (e) not having an acidic group. Furthermore, relative to 100 parts by mass of the total amount of the monomers, it preferably contains 0.001 to 30 parts by mass of a water-soluble photopolymerization initiator system (d), 0.001 to 30 parts by mass of a non-water-soluble photopolymerization initiator system (f), and 0 to 100 parts by mass of a filler (g), and it is more preferable that it contains 0.05 to 10 parts by mass of the water-soluble photopolymerization initiator system (d), 0.05 to 10 parts by mass of the non-water-soluble photopolymerization initiator system (f), and 1 to 50 parts by mass of a filler (g).
[0138] <Self-adhesive dental composite resin> In the present invention, the non-solvent dental adhesive composition (B) is also used as a self-adhesive dental composite resin, which is one of the preferred embodiments. In particular, in recent years, composite resins that have adhesive properties in filling composite resins have been developed, and the process is further simplified compared to the adhesive system of the dental bonding material described above, so that the merits of use are great. When the non-solvent dental adhesive composition (B) of the present invention is used as a self-adhesive dental composite resin, it is preferable that it contains a monomer (b) having an acidic group, a hydrophobic monomer (c) having no acidic group, a hydrophilic monomer (e) having no acidic group, a water-soluble photopolymerization initiator system (d), a non-water-soluble photopolymerization initiator system (f), and a filler (g).
[0139] The content of each component in the self-adhesive dental composite resin is preferably 1 to 90 parts by mass of monomer (b) having an acidic group, 1 to 90 parts by mass of hydrophobic monomer (c) not having an acidic group, and 0 to 90 parts by mass of hydrophilic monomer (e) not having an acidic group, relative to 100 parts by mass of the total amount of monomers in the non-solvent-based dental adhesive composition (B), and more preferably 5 to 80 parts by mass of monomer (b) having an acidic group, 5 to 80 parts by mass of hydrophobic monomer (c) not having an acidic group, and 1 to 80 parts by mass of hydrophilic monomer (e) not having an acidic group. Furthermore, relative to 100 parts by mass of the total amount of the monomers, it is preferable that the composition contains 0.001 to 30 parts by mass of a water-soluble photopolymerization initiator system (d), 0.001 to 30 parts by mass of a non-water-soluble photopolymerization initiator system (f), and 50 to 2000 parts by mass of a filler (g), and it is more preferable that the composition contains 0.05 to 10 parts by mass of the water-soluble photopolymerization initiator system (d), 0.05 to 10 parts by mass of the non-water-soluble photopolymerization initiator system (f), and 100 to 1500 parts by mass of a filler (g). On the other hand, in order to exhibit high initial adhesive strength, adhesive durability, and dentin cohesive fracture rate even to tooth tissue in a dry state, the non-solvent-based dental adhesive composition (B) preferably contains 1 to 90 parts by mass of a monomer (b) having an acidic group, 1 to 99 parts by mass of a hydrophobic monomer (c) not having an acidic group, and 0 to 90 parts by mass of a hydrophilic monomer (e) not having an acidic group, per 100 parts by mass of the total amount of monomers, more preferably contains 1 to 80 parts by mass of a monomer (b) having an acidic group, 10 to 99 parts by mass of a hydrophobic monomer (c) not having an acidic group, and 0 to 80 parts by mass of a hydrophilic monomer (e) not having an acidic group, and even more preferably contains 1 to 80 parts by mass of a monomer (b) having an acidic group, 10 to 99 parts by mass of a hydrophobic monomer (c) not having an acidic group, and 0 to 50 parts by mass of a hydrophilic monomer (e) not having an acidic group. Furthermore, relative to 100 parts by mass of the total amount of the monomers, it is preferable that the composition contains 0.001 to 30 parts by mass of a water-soluble photopolymerization initiator system (d), 0.001 to 30 parts by mass of a non-water-soluble photopolymerization initiator system (f), and 50 to 2000 parts by mass of a filler (g), and it is more preferable that the composition contains 0.05 to 10 parts by mass of the water-soluble photopolymerization initiator system (d), 0.05 to 10 parts by mass of the non-water-soluble photopolymerization initiator system (f), and 100 to 1500 parts by mass of a filler (g).
[0140] <Dental cement> In the present invention, the non-solvent dental adhesive composition (B) is also used as a dental cement in one preferred embodiment. Suitable examples of dental cement include resin cement, glass ionomer cement, and resin-reinforced glass ionomer cement. The dental cement may be used with a self-etching primer as a pretreatment material.
[0141] The content of each component in the dental cement is preferably 1 to 90 parts by mass of monomer (b) having an acidic group, 1 to 90 parts by mass of hydrophobic monomer (c) having no acidic group, and 0 to 90 parts by mass of hydrophilic monomer (f) having no acidic group, relative to 100 parts by mass of the total amount of monomers in the non-solvent-based dental adhesive composition (B), and more preferably 5 to 80 parts by mass of monomer (b) having an acidic group, 5 to 80 parts by mass of hydrophobic monomer (c) having no acidic group, and 1 to 80 parts by mass of hydrophilic monomer (e) having no acidic group. Furthermore, relative to 100 parts by mass of the total amount of the monomers, it is preferable that the composition contains 0.001 to 30 parts by mass of a water-soluble photopolymerization initiator system (d), 0.001 to 30 parts by mass of a non-water-soluble photopolymerization initiator system (f), and 50 to 2000 parts by mass of a filler (g), and it is more preferable that the composition contains 0.05 to 10 parts by mass of the water-soluble photopolymerization initiator system (d), 0.05 to 10 parts by mass of the non-water-soluble photopolymerization initiator system (f), and 100 to 1500 parts by mass of a filler (g). On the other hand, in order to exhibit high initial adhesive strength and adhesive durability even to tooth tissue in a dry state, the non-solvent-based dental adhesive composition (B) preferably contains 1 to 90 parts by mass of a monomer (b) having an acidic group, 1 to 99 parts by mass of a hydrophobic monomer (c) not having an acidic group, and 0 to 90 parts by mass of a hydrophilic monomer (e) not having an acidic group, per 100 parts by mass of the total amount of monomers, more preferably contains 1 to 80 parts by mass of a monomer (b) having an acidic group, 10 to 99 parts by mass of a hydrophobic monomer (c) not having an acidic group, and 0 to 80 parts by mass of a hydrophilic monomer (e) not having an acidic group, and even more preferably contains 1 to 80 parts by mass of a monomer (b) having an acidic group, 10 to 99 parts by mass of a hydrophobic monomer (c) not having an acidic group, and 0 to 50 parts by mass of a hydrophilic monomer (e) not having an acidic group. Furthermore, relative to 100 parts by mass of the total amount of the monomers, it is preferable that the composition contains 0.001 to 30 parts by mass of a water-soluble photopolymerization initiator system (d), 0.001 to 30 parts by mass of a non-water-soluble photopolymerization initiator system (f), and 50 to 2000 parts by mass of a filler (g), and it is more preferable that the composition contains 0.05 to 10 parts by mass of the water-soluble photopolymerization initiator system (d), 0.05 to 10 parts by mass of the non-water-soluble photopolymerization initiator system (f), and 100 to 1500 parts by mass of a filler (g).
[0142] In any of the preferred embodiments of the dental bonding material, self-adhesive dental composite resin, and dental cement described above, the content of each component can be appropriately changed based on the explanation in the above specification, and any component can be added, deleted, or otherwise modified.
[0143] As described above, the non-solvent-based dental adhesive composition (B) of the present invention can tolerate trace amounts of water or organic solvent (for example, 3% by mass or less of the composition) as long as this does not cause inconveniences such as poor curing or delayed curing, and the content of water and organic solvent in the composition is preferably 1% by mass or less, and more preferably 0.1% by mass or less.
[0144] The present invention includes embodiments in which the above configurations are combined in various ways within the scope of the technical concept of the present invention, as long as the effects of the present invention are achieved. EXAMPLES
[0145] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples. In addition, not all of the combinations of features described in the examples are necessarily essential to the solution of the present invention. The various components used in the following examples and comparative examples, their abbreviations, structures, and test methods are as follows:
[0146] [Dental cleaning materials (A)] ADG: AD gel (a gel-like aqueous solution containing 10 to 15% by mass of sodium hypochlorite, which is an alkali metal hypochlorite (a), manufactured by Kuraray Noritake Dental Co., Ltd.) ANT: Dental Antiformin (an aqueous solution containing 3 to 6% by mass of sodium hypochlorite, which is an alkali metal hypochlorite (a), manufactured by Nippon Dental Pharmaceuticals Co., Ltd.)
[0147] [Non-solvent-based dental adhesive composition (B)] [Monomer having an acidic group (b)] MDP: 10-methacryloyloxydecyl dihydrogen phosphate
[0148] [Hydrophobic monomer having no acidic group (c)] Bis-GMA: 2,2-bis[4-(3-methacryloyloxy-2-hydroxypropoxy)phenyl]propane UDMA: 2,2,4-trimethylhexamethylenebis(2-carbamoyloxyethyl)dimethacrylate 3G: Triethylene glycol dimethacrylate DD: 1,10-decanediol dimethacrylate MAEA: N-methacryloyloxyethyl acrylamide
[0149] [Water-soluble photoinitiator system (d)] Water-soluble cleavable photoinitiator (d-1) Li-TPO: Lithium phenyl(2,4,6-trimethylbenzoyl)phosphinate (compound represented by the following formula (6)) [ka] Solubility in water at 25℃: 45g / L
[0150] Na-TPO: phenyl(2,4,6-trimethylbenzoyl)phosphinic acid sodium salt (compound represented by the following formula (7)) [ka] Solubility in water at 25°C: 28g / L
[0151] BAPO-OLi: bis(2,4,6-trimethylbenzoyl)phosphinic acid lithium salt (compound represented by the following formula (8)) [ka] Solubility in water at 25°C: 52g / L
[0152] BAPO-ONa: bis(2,4,6-trimethylbenzoyl)phosphinic acid sodium salt (compound represented by the following formula (9)) [ka] Solubility in water at 25℃: 60g / L
[0153] Water-soluble photosensitizer (d-2) CQ-COONa (compound represented by the following formula (10)) [ka] Solubility in water at 25℃:>10g / L
[0154] Non-water-soluble reducing agent (d-3) DABE: Ethyl 4-(N,N-dimethylamino)benzoate Solubility in water at 25℃: <1g / L
[0155] Non-water-soluble photosensitizer (d-4) CQ: dl-camphorquinone Solubility in water at 25°C: 1.7g / L
[0156] Water-soluble reducing agent (d-5) AMN-COOLi (compound represented by the following formula (11)) [ka] Solubility in water at 25℃:>10g / L
[0157] [Hydrophilic monomer (e) having no acidic group] HEMA: 2-hydroxyethyl methacrylate DEAA: N,N-diethylacrylamide
[0158] [Non-water-soluble photopolymerization initiator (f-1)] TMDPO-A1 (compound represented by the following formula (12)) [ka] Solubility in water at 25℃: <10g / L
[0159] BAPO-A1 (compound represented by the following formula (13)) [ka] Solubility in water at 25℃: <10g / L
[0160] TMDPO: 2,4,6-trimethylbenzoyldiphenylphosphine oxide Solubility in water at 25℃: <1g / L BAPO: Bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide Solubility in water at 25℃: <1g / L
[0161] [Filler (g)] Inorganic filler 1: fine silica particle "Aerosil (registered trademark) R 972" manufactured by Nippon Aerosil Co., Ltd., average particle size: 16 nm Inorganic filler 2: fine silica particle "Aerosil (registered trademark) 380" manufactured by Nippon Aerosil Co., Ltd., average particle size: 7 nm Inorganic filler 3: Silane-treated silica powder Silica powder (manufactured by Nichitsu Co., Ltd., product name: Hi-Silica) was pulverized in a ball mill to obtain pulverized silica powder. The average particle size of the obtained pulverized silica powder was measured on a volume basis using a laser diffraction type particle size distribution measuring device (manufactured by Shimadzu Corporation, model "SALD-2300") and was found to be 2.2 μm. 100 parts by mass of this pulverized silica powder was surface-treated with 4 parts by mass of γ-methacryloyloxypropyltrimethoxysilane by a conventional method to obtain silane-treated silica powder. Inorganic filler 4: Silane-treated barium glass powder Barium glass (manufactured by Estec, product name "E-3000") was pulverized in a ball mill to obtain barium glass powder. The average particle size of the obtained barium glass powder was measured on a volume basis using a laser diffraction type particle size distribution measuring device (manufactured by Shimadzu Corporation, model "SALD-2300") and found to be 2.4 μm. 100 parts by mass of this barium glass powder was surface-treated with 3 parts by mass of γ-methacryloyloxypropyltrimethoxysilane by a conventional method to obtain silane-treated barium glass powder.
[0162] [others] BHT: 2,6-di-t-butyl-4-methylphenol (stabilizer (polymerization inhibitor))
[0163] [Examples 1-1 to 1-19 and Comparative Examples 1-1 to 1-5] <Application of a non-solvent dental adhesive composition to a dental bonding material on a tooth surface cleaned with a dental cleaning material> The dental bonding materials of Examples 1-1 to 1-19 and Comparative Examples 1-1 to 1-5 were prepared by mixing and dispersing the components described in Tables 1 and 2 at room temperature using the above-mentioned components. The tensile bond strength to dentin and durability against repeated load were then measured using the dental bonding materials obtained according to the methods described below. Tables 1 and 2 show the compounding ratios (parts by mass) and test results of the dental bonding materials of each Example and Comparative Example.
[0164] [Tensile bond strength to wet dentin] The labial surface of a bovine mandibular anterior tooth was polished with #80 silicon carbide paper (manufactured by Nihon Kenshi Co., Ltd.) under running water to obtain a sample with the flat surface of the dentin exposed. The obtained sample was further polished with #1000 silicon carbide paper (manufactured by Nihon Kenshi Co., Ltd.) under running water. After polishing, the water on the surface was dried by air blowing.
[0165] After drying, a dental cleaning agent was applied to the smooth surface, which was left for 1 minute and then washed with running water. After washing, the water on the surface was dried by blowing air on it.
[0166] After drying, a 150 μm thick adhesive tape with a 3 mm diameter hole was attached to the smooth surface to determine the adhesive area. Water-soaked absorbent cotton was applied to the adhesive surface inside the hole to form a layer of glossy surface.
[0167] The dental bonding material prepared in each Example and Comparative Example was applied to the round hole with a brush, left for 10 seconds, and then the surface was air-blown.The dental bonding material was then cured by irradiating it with light for 10 seconds using a dental LED light irradiator (manufactured by Ultradent, product name "VALO").
[0168] The surface of the obtained hardened dental bonding material was filled with dental filling composite resin (manufactured by Kuraray Noritake Dental Co., Ltd., product name "Clearfil (registered trademark) AP-X") and covered with a release film (polyester). Next, a slide glass was placed on the release film and pressed against it to smooth the applied surface of the composite resin. Next, the composite resin was irradiated with light for 20 seconds using the irradiator "VALO" through the release film to harden the composite resin.
[0169] For 10 of the 20 samples, one end face (circular cross section) of a stainless steel cylindrical rod (diameter 7 mm, length 2.5 cm) was bonded to the surface of the bonded hardened dental filling composite resin using a commercially available dental resin cement (manufactured by Kuraray Noritake Dental Co., Ltd., product name "Panavia (registered trademark) 21"). After bonding, the sample was left at room temperature for 30 minutes and then immersed in distilled water to obtain a test sample for the initial adhesive strength test. The sample was left at rest for 24 hours in an incubator maintained at 37°C. To evaluate the initial adhesive strength, the tensile adhesive strength was measured immediately after leaving it for 24 hours.
[0170] For the remaining 10 pieces, in order to evaluate the adhesion durability against repeated load, a compressive load of 10 kgf was applied to the center of the surface of the hardened dental filling composite resin with a spherical tip indenter, with a frequency of 1 Hz, and 100,000 repetitions. Then, one end face (circular cross section) of a stainless steel cylindrical rod (diameter 7 mm, length 2.5 cm) was bonded to the surface of the hardened dental filling composite resin using a commercially available dental resin cement (manufactured by Kuraray Noritake Dental Co., Ltd., product name "Panavia (registered trademark) 21"). After bonding, the sample was left at room temperature for 30 minutes and then immersed in distilled water to obtain a test sample for the initial adhesive strength test. After leaving it for 24 hours in an incubator maintained at 37 ° C, the tensile adhesive strength was measured.
[0171] The tensile adhesive strength of the test samples for the adhesion test was measured using a universal testing machine (manufactured by Shimadzu Corporation) with a crosshead speed set at 2 mm / min, and the average value was taken as the tensile adhesive strength.
[0172] [Comparative Example 1-6] <Application of a non-solvent dental adhesive composition to a dental bonding material on a tooth surface that has not been cleaned with a dental cleaning material> The test was carried out in the same manner as in Example 1-1, except that the same non-solvent-based dental adhesive composition as in Example 1-1 was used as the dental bonding material and cleaning of the adhesion surface with the dental cleaning material (A) was omitted.
[0173] [Table 1]
[0174] [Table 2]
[0175] As shown in Tables 1 and 2, the dental bonding materials according to the present invention (Examples 1-1 to 1-19) exhibited an initial adhesive strength of 15.2 MPa or more and an adhesive durability of 13.6 MPa or more to dentin cleaned with the dental cleaning material according to the present invention. In contrast, as shown in Table 2, the dental bonding materials not containing the water-soluble photopolymerization initiator system (d) (Comparative Examples 1-1 to 1-5) exhibited an initial adhesive strength of 11.7 MPa or less and an adhesive durability of 8.2 MPa or less to dentin. Furthermore, when cleaning with the dental cleaning material according to the present invention was omitted, as shown in Comparative Example 1-6, a high initial adhesive strength of 18.4 MPa was obtained, but the adhesive strength after repeated loading decreased to 10.5 MPa or less, confirming that the polymerization hardening properties at the interface and inside the resin-impregnated layer were insufficient.
[0176] [Examples 2-1 to 2-19 and Comparative Examples 2-1 to 2-5] <Application of a non-solvent-based dental adhesive composition to a self-adhesive dental composite resin on a tooth surface cleaned with a dental cleaning material> Using the above-mentioned components, the components shown in Tables 3 and 4 were mixed and kneaded at room temperature to prepare the self-adhesive dental composite resins of Examples 2-1 to 2-19 and Comparative Examples 2-1 to 2-5. Next, the tensile bond strength to dentin was measured using these self-adhesive dental composite resins according to the method described below. Tables 3 and 4 show the compounding ratios (parts by mass) and test results of the self-adhesive dental composite resins of each Example and Comparative Example.
[0177] [Tensile bond strength to wet dentin] The labial surface of a bovine mandibular anterior tooth was polished with #80 silicon carbide paper (manufactured by Nihon Kenshi Co., Ltd.) under running water to obtain a sample with the flat surface of the dentin exposed. The obtained sample was further polished with #1000 silicon carbide paper (manufactured by Nihon Kenshi Co., Ltd.) under running water. After polishing, the water on the surface was dried by air blowing.
[0178] After drying, a dental cleaning agent was applied to the smooth surface, which was left for 1 minute and then washed with running water. After washing, the water on the surface was dried by blowing air on it.
[0179] After drying, a 150 μm thick adhesive tape with a 3 mm diameter hole was attached to the smooth surface to determine the adhesive area. Water-soaked absorbent cotton was applied to the adhesive surface inside the hole to form a layer of glossy surface.
[0180] The self-adhesive dental composite resin prepared in each Example and Comparative Example was filled into the round hole and covered with a release film (polyester). Next, a slide glass was placed on the release film and pressed against it to smooth the coated surface of the self-adhesive dental composite resin. Next, the self-adhesive dental composite resin was irradiated with light for 10 seconds using a dental LED light irradiator (manufactured by Ultradent, product name "VALO") through the release film to harden the self-adhesive dental composite resin.
[0181] For 10 of the 20 samples, one end face (circular cross section) of a stainless steel cylindrical rod (diameter 7 mm, length 2.5 cm) was bonded to the surface of the cured self-adhesive dental composite resin bonded with a commercially available dental resin cement (manufactured by Kuraray Noritake Dental Co., Ltd., product name "Panavia (registered trademark) 21"). After bonding, the sample was left at room temperature for 30 minutes and then immersed in distilled water to obtain a test sample for the initial adhesive strength test. The sample was left at rest for 24 hours in an incubator maintained at 37°C. To evaluate the initial adhesive strength, the tensile adhesive strength was measured immediately after leaving it for 24 hours.
[0182] For the remaining 10 pieces, in order to evaluate the adhesion durability against repeated load, a compressive load of 10 kgf was applied to the center of the surface of the cured self-adhesive dental composite resin with a spherical tip indenter, and the number of repetitions was 100,000 times at a frequency of 1 Hz. Then, one end face (circular cross section) of a stainless steel cylindrical rod (diameter 7 mm, length 2.5 cm) was bonded to the surface of the cured self-adhesive dental composite resin using a commercially available dental resin cement (manufactured by Kuraray Noritake Dental Co., Ltd., product name "Panavia (registered trademark) 21"). After bonding, the sample was left at room temperature for 30 minutes and then immersed in distilled water to obtain a test sample for the initial adhesive strength test. After leaving it for 24 hours in an incubator maintained at 37 ° C, the tensile adhesive strength was measured.
[0183] The tensile adhesive strength of the test samples for the adhesion test was measured using a universal testing machine (manufactured by Shimadzu Corporation) with a crosshead speed set at 2 mm / min, and the average value was taken as the tensile adhesive strength.
[0184] [Comparative Example 2-6] <Application of a non-solvent-based dental adhesive composition to a self-adhesive dental composite resin on a tooth surface that has not been cleaned with a dental cleaning material> The same non-solvent-based dental adhesive composition as in Example 2-1 was used as the self-adhesive dental composite resin, and the test was carried out in the same manner as in Example 2-1, except that cleaning of the adhesion surface with dental cleaning material (A) was omitted.
[0185] [Table 3]
[0186] [Table 4]
[0187] As shown in Tables 3 and 4, the self-adhesive dental composite resins according to the present invention (Examples 1-1 to 1-19) exhibited an initial adhesive strength of 14 MPa or more and an adhesive durability of 12.1 MPa or more to the dentin cleaned with the dental cleaning material according to the present invention. In contrast, as shown in Table 4, the dental bonding materials (Comparative Examples 2-1 to 2-5) not including the water-soluble photopolymerization initiator system (d) exhibited an initial adhesive strength of 7.5 MPa or less and an adhesive durability of 5.0 MPa or less to the dentin. In addition, when cleaning with the dental cleaning material according to the present invention was omitted, as shown in Comparative Example 2-6, the initial adhesive strength was as high as 15.6 MPa, but after repeated loading, it decreased to 7.1 MPa, confirming that the polymerization hardening property of the interface and the inside of the resin-impregnated layer was insufficient.
[0188] [Examples 3-1 to 3-17 and Comparative Examples 3-1 to 3-5] <Application of a non-solvent dental adhesive composition to a dental bonding material on a tooth surface cleaned with a dental cleaning material> The dental bonding materials of Examples 3-1 to 3-17 and Comparative Examples 3-1 to 3-5 were prepared by mixing and dispersing the components shown in Tables 5 and 6 at room temperature using the above-mentioned components. The tensile bond strength to dentin of the obtained dental bonding materials was then measured according to the method described below. Tables 5 and 6 show the compounding ratios (parts by mass) and test results of the dental bonding materials of each Example and Comparative Example.
[0189] [Tensile bond strength to dry dentin] The labial surface of a bovine mandibular anterior tooth was polished with #80 silicon carbide paper (manufactured by Nihon Kenshi Co., Ltd.) under running water to obtain a sample with the flat surface of the dentin exposed. The obtained sample was further polished with #1000 silicon carbide paper (manufactured by Nihon Kenshi Co., Ltd.) under running water. After polishing, the water on the surface was dried by air blowing.
[0190] After drying, a dental cleaning agent was applied to the smooth surface, which was left for 1 minute and then washed with running water. After washing, the water on the surface was dried by blowing air on it.
[0191] After drying, a piece of adhesive tape with a thickness of about 150 μm and a round hole with a diameter of 3 mm was attached to the smooth surface to define the adhesive area.
[0192] The dental bonding material prepared in each Example and Comparative Example was applied to the round hole with a brush, left for 10 seconds, and then the surface was air-blown.The dental bonding material was then cured by irradiating it with light for 10 seconds using a dental LED light irradiator (manufactured by Ultradent, product name "VALO").
[0193] The surface of the obtained hardened dental bonding material was filled with dental filling composite resin (manufactured by Kuraray Noritake Dental Co., Ltd., product name "Clearfil (registered trademark) AP-X") and covered with a release film (polyester). Next, a slide glass was placed on the release film and pressed against it to smooth the applied surface of the composite resin. Next, the composite resin was irradiated with light for 20 seconds using the irradiator "VALO" through the release film to harden the composite resin.
[0194] For 10 of the 20 samples, one end face (circular cross section) of a stainless steel cylindrical rod (diameter 7 mm, length 2.5 cm) was bonded to the surface of the bonded hardened dental filling composite resin using a commercially available dental resin cement (manufactured by Kuraray Noritake Dental Co., Ltd., product name "Panavia (registered trademark) 21"). After bonding, the sample was left at room temperature for 30 minutes and then immersed in distilled water to obtain a test sample for the initial adhesive strength test. The sample was left at rest for 24 hours in an incubator maintained at 37°C. To evaluate the initial adhesive strength, the tensile adhesive strength was measured immediately after leaving it for 24 hours.
[0195] For the remaining 10 pieces, in order to evaluate the adhesion durability against repeated load, a compressive load of 10 kgf was applied to the center of the surface of the hardened dental filling composite resin with a spherical tip indenter, with a frequency of 1 Hz, and 100,000 repetitions. Then, one end face (circular cross section) of a stainless steel cylindrical rod (diameter 7 mm, length 2.5 cm) was bonded to the surface of the hardened dental filling composite resin using a commercially available dental resin cement (manufactured by Kuraray Noritake Dental Co., Ltd., product name "Panavia (registered trademark) 21"). After bonding, the sample was left at room temperature for 30 minutes and then immersed in distilled water to obtain a test sample for the initial adhesive strength test. After leaving it for 24 hours in an incubator maintained at 37 ° C, the tensile adhesive strength was measured.
[0196] The tensile adhesive strength of the test samples for the adhesion test was measured using a universal testing machine (Autograph AG-I 100 kN, manufactured by Shimadzu Corporation) with a crosshead speed set to 2 mm / min, and the average value was taken as the tensile adhesive strength.
[0197] [Comparative Example 3-6] <Application of a non-solvent dental adhesive composition to a dental bonding material on a tooth surface that has not been cleaned with a dental cleaning material> The test was carried out in the same manner as in Example 3-1, except that the same non-solvent-based dental adhesive composition as in Example 3-1 was used as the dental bonding material and cleaning of the adhesion surface with the dental cleaning material (A) was omitted.
[0198] [Table 5]
[0199] [Table 6]
[0200] As shown in Tables 5 and 6, the dental bonding materials according to the present invention (Examples 3-1 to 3-17) exhibited an initial adhesive strength of 13.8 MPa or more and an adhesive durability of 13.5 MPa or more to dentin after drying. In contrast, as shown in Table 6, the dental bonding materials not including the water-soluble photopolymerization initiator system (d) (Comparative Examples 3-1 to 3-5) exhibited an initial adhesive strength of 10.8 MPa or less to dentin and an adhesive durability of 8.8 MPa or less. Furthermore, when cleaning with the dental cleaning material according to the present invention was omitted, as shown in Comparative Example 3-6, the initial adhesive strength was a high value of 16.4 MPa, but after repeated loading, it decreased to 7.8 MPa, confirming that the polymerization hardening property at the interface and inside the resin-impregnated layer was insufficient.
[0201] [Examples 4-1 to 4-16 and Comparative Examples 4-1 to 4-5] <Application of non-solvent-based dental adhesive composition to self-adhesive dental composite resin> Using the above-mentioned components, the components shown in Tables 7 and 8 were mixed and kneaded at room temperature to prepare the self-adhesive dental composite resins of Examples 4-1 to 4-16 and Comparative Examples 4-1 to 4-5. Next, the tensile bond strength to dentin was measured using these self-adhesive dental composite resins according to the method described below. Tables 7 to 8 show the compounding ratios (parts by mass) and test results of the self-adhesive dental composite resins of each Example and Comparative Example.
[0202] [Tensile bond strength to dry dentin] The labial surface of a bovine mandibular anterior tooth was polished with #80 silicon carbide paper (manufactured by Nihon Kenshi Co., Ltd.) under running water to obtain a sample with the flat surface of the dentin exposed. The obtained sample was further polished with #1000 silicon carbide paper (manufactured by Nihon Kenshi Co., Ltd.) under running water. After polishing, the water on the surface was dried by air blowing.
[0203] After drying, a dental cleaning agent was applied to the smooth surface, which was left for 1 minute and then washed with running water. After washing, the water on the surface was dried by blowing air on it.
[0204] After drying, a piece of adhesive tape with a thickness of about 150 μm and a round hole with a diameter of 3 mm was attached to the smooth surface to define the adhesive area.
[0205] The self-adhesive dental composite resin prepared in each Example and Comparative Example was filled into the round hole and covered with a release film (polyester). Next, a slide glass was placed on the release film and pressed against it to smooth the coated surface of the self-adhesive dental composite resin. Next, the self-adhesive dental composite resin was irradiated with light for 10 seconds using a dental LED light irradiator (manufactured by Ultradent, product name "VALO") through the release film to harden the self-adhesive dental composite resin.
[0206] For 10 of the 20 samples, one end face (circular cross section) of a stainless steel cylindrical rod (diameter 7 mm, length 2.5 cm) was bonded to the surface of the cured self-adhesive dental composite resin bonded with a commercially available dental resin cement (manufactured by Kuraray Noritake Dental Co., Ltd., product name "Panavia (registered trademark) 21"). After bonding, the sample was left at room temperature for 30 minutes and then immersed in distilled water to obtain a test sample for the initial adhesive strength test. The sample was left at rest for 24 hours in an incubator maintained at 37°C. To evaluate the initial adhesive strength, the tensile adhesive strength was measured immediately after leaving it for 24 hours.
[0207] For the remaining 10 pieces, in order to evaluate the adhesion durability against repeated load, a compressive load of 10 kgf was applied to the center of the surface of the cured self-adhesive dental composite resin with a spherical tip indenter, and the number of repetitions was 100,000 times at a frequency of 1 Hz. Then, one end face (circular cross section) of a stainless steel cylindrical rod (diameter 7 mm, length 2.5 cm) was bonded to the surface of the cured self-adhesive dental composite resin using a commercially available dental resin cement (manufactured by Kuraray Noritake Dental Co., Ltd., product name "Panavia (registered trademark) 21"). After bonding, the sample was left at room temperature for 30 minutes and then immersed in distilled water to obtain a test sample for the initial adhesive strength test. After leaving it for 24 hours in an incubator maintained at 37 ° C, the tensile adhesive strength was measured.
[0208] The tensile adhesive strength of the test samples for the adhesion test was measured using a universal testing machine (manufactured by Shimadzu Corporation) with a crosshead speed set at 2 mm / min, and the average value was taken as the tensile adhesive strength.
[0209] [Comparative Example 4-6] <Application of a non-solvent-based dental adhesive composition to a self-adhesive dental composite resin on a tooth surface that has not been cleaned with a dental cleaning material> The same non-solvent-based dental adhesive composition as in Example 4-1 was used as the self-adhesive dental composite resin, and the test was carried out in the same manner as in Example 4-1, except that cleaning of the adhesion surface with dental cleaning material (A) was omitted.
[0210] [Table 7]
[0211] [Table 8]
[0212] As shown in Tables 7 and 8, the self-adhesive dental composite resins according to the present invention (Examples 4-1 to 4-16) exhibited an initial adhesive strength of 12.9 MPa or more and an adhesive durability of 11.5 MPa or more to dentin after drying. In contrast, as shown in Table 8, the dental bonding materials not containing the water-soluble photopolymerization initiator system (d) (Comparative Examples 4-1 to 4-5) exhibited an initial adhesive strength of 7.6 MPa or less to dentin and an adhesive durability of 54.7 MPa or less. Furthermore, when cleaning with the dental cleaning material according to the present invention was omitted, as shown in Comparative Example 4-6, the initial adhesive strength was a high value of 13.5 MPa or more, but after repeated loading, it decreased to 6.6 MPa, confirming that the polymerization hardening property at the interface and inside the resin-impregnated layer was insufficient. [Industrial Applicability]
[0213] The adhesive dental material kit comprising the dental cleaning material and the non-solvent-based dental adhesive composition according to the present invention as components thereof is suitably used in the field of dental care as an adhesive dental material kit consisting of a dental cleaning material and a dental bonding material, a self-adhesive dental composite resin, or a dental cement.
Claims
1. A dental cleaning material (A) containing an alkali metal hypochlorite (a); A non-solvent-based dental adhesive composition (B) containing a monomer (b) having an acidic group, a hydrophobic monomer (c) not having an acidic group, and a water-soluble photopolymerization initiator system (d) having a solubility in water at 25°C of 10 g / L or more; An adhesive dental material kit comprising:
2. 2. The adhesive dental material kit according to claim 1, wherein the alkali metal hypochlorite (a) comprises sodium hypochlorite.
3. 3. The adhesive dental material kit according to claim 1, wherein the dental cleaning material (A) comprises an aqueous solution containing 1 to 20% by mass of the alkali metal hypochlorite (a).
4. The adhesive dental material kit according to any one of claims 1 to 3, wherein the water-soluble photopolymerization initiator system (d) comprises a water-soluble cleavage-type photopolymerization initiator (d-1) having a solubility in water at 25°C of 10 g / L or more.
5. The adhesive dental material kit according to claim 4, wherein the water-soluble cleavable photopolymerization initiator (d-1) is at least one selected from the group consisting of compounds represented by general formula (1) and compounds represented by general formula (2). 【Chemistry 1】 【Chemistry 2】 [In the formula, R 1 , R 2 , R 3 , R 4 , R 5 , and R 6 are each independently a linear or branched alkyl group having 1 to 4 carbon atoms or a halogen atom, M is a hydrogen ion, an alkali metal ion, an alkaline earth metal ion, a magnesium ion, a pyridinium ion (the pyridine ring may have a substituent), or HN + Z 1 Z 2 Z 3 (In the formula, Z 1 , Z 2 , and Z 3 are each independently an organic group or a hydrogen atom), and n represents 1 or 2.
6. The adhesive dental material kit according to claim 4 or 5, further comprising a water-insoluble reducing agent (d-3) having a solubility in water at 25° C. of less than 10 g / L and a water-insoluble photosensitizer (d-4) having a solubility in water at 25° C. of less than 10 g / L.
7. The adhesive dental material kit according to any one of claims 1 to 3, wherein the water-soluble photopolymerization initiator system (d) comprises a water-soluble photosensitizer (d-2) having a solubility in water at 25°C of 10 g / L or more and a water-insoluble reducing agent (d-3) having a solubility in water at 25°C of less than 10 g / L.
8. The adhesive dental material kit according to any one of claims 1 to 3, wherein the water-soluble photopolymerization initiator system (d) comprises a water-insoluble photosensitizer (d-4) having a solubility in water at 25°C of less than 10 g / L and a water-soluble reducing agent (d-5) having a solubility in water at 25°C of 10 g / L or more.
9. The adhesive dental material kit according to any one of claims 1 to 3, wherein the water-soluble photopolymerization initiator system (d) comprises a water-soluble photosensitizer (d-2) having a solubility in water at 25°C of 10 g / L or more and a water-soluble reducing agent (d-5) having a solubility in water at 25°C of 10 g / L or more.
10. The adhesive dental material kit according to any one of claims 1 to 9, wherein the non-solvent-based dental adhesive composition (B) further comprises a hydrophilic monomer (e) having no acidic group.
11. The adhesive dental material kit according to claim 10, wherein the content of the hydrophilic monomer (e) not having an acidic group is 50 mass% or less relative to the total mass of the hydrophobic monomer (c) not having an acidic group and the hydrophilic monomer (e) not having an acidic group.
12. The adhesive dental material kit according to any one of claims 1 to 11, wherein the monomer (b) having an acidic group includes a monomer having a phosphate group.
13. The adhesive dental material kit according to any one of claims 1 to 12, wherein the non-solvent-based dental adhesive composition (B) further comprises a non-water-soluble photopolymerization initiator system (f) having a solubility in water at 25°C of less than 10 g / L.
14. The adhesive dental material kit according to claim 13, wherein in the non-solvent-based dental adhesive composition (B), the mass ratio [(d):(f)] of the water-soluble photopolymerization initiator system (d) to the water-insoluble photopolymerization initiator system (f) is 10:1 to 1:
10.
15. The adhesive dental material kit according to any one of claims 1 to 14, wherein the non-solvent-based dental adhesive composition (B) is a dental bonding material.
16. The adhesive dental material kit according to any one of claims 1 to 14, wherein the non-solvent-based dental adhesive composition (B) is a self-adhesive dental composite resin.
17. The adhesive dental material kit according to any one of claims 1 to 14, wherein the non-solvent-based dental adhesive composition (B) is a dental cement.
Citation Information
Patent Citations
Dental resin material
JP1987226907A
Aqueous photo-setting type adhesive composition
JP1992154708A
Dental adhesive material set
JP2000186010A
Method for Improving Penetration or Long Term Adhesion of Compositions to Dental Tissues and Compositions Usable in Said Method
US20140050674A1
Camphorquinone derivative having acylphosphine oxide group, and containing the same, photopolymerization catalyst and photo / chemical polymerization catalyst, and containing these, hardenable composition
WO2007105296A1